ARHI as a key regulator of EMT and metastasis in pancreatic cancer via the Notch-1 pathway - Jingjing Liu; Yiqun Zhao; Ying Wang; Ying Shi; Qiang Zhi; Linlin Chen; Yuhao Ke; Jianlin Ren (Human Genetics, 2026)

Adsorption behavior of amine-based strong base anion exchange resin in complex Mo(VI)-W(VI) solutions - Han Zhao; Linlin Tong; Jian Kang; Hongying Yang (Hydrometallurgy, 2026)

Synthesis and characterization of porous carbon from Hawaii nut shells for effective CO2 capture - Xiaohan Liu; Yingyi Wang; Zhentao Chen; Xin Hu; Qiang Xiao; Leihong Zhao; Muslum Demir; Murat Kilic; Mohammed K. Al Mesfer; Linlin Wang (Biomass and Bioenergy, 2026)

Artificial intelligence-driven food labels: Technological convergence, application innovation, and sustainable future - Linlin Zhao; Xingyu Chen; Wenqin Gu; Huinan Jiang; Bimal Chitrakar; Xiangren Meng (Trends in Food Science & Technology, 2026)

Development of low-ammonia MICP technology based on Mg2 +-enhanced nitrogen assimilation and biomineralization - Linlin Zhang; Yue Zhao; Hongyu Han; Ruoxi Li; Zhaofeng Liu; Yuqing Li; Shenghui Yang; Wen Nie (Journal of Environmental Chemical Engineering, 2026)

Ultramicroporous N-doped carbons prepared by KHC2O4 activation for CO2 adsorption - Yujia Yin; Yingyi Wang; Ziyun Li; Ya Liu; Leihong Zhao; Muslum Demir; Aseel Zaid; Linlin Wang; Xin Hu (Journal of Environmental Chemical Engineering, 2026)

Synergistic acid pretreatment and ball milling activation for KMnO4-enhanced H2SO4-H3PO4 oxidative leaching of low-grade complex tungsten-molybdenum ore - Han Zhao; Linlin Tong; Jian Kang; Hongying Yang (Hydrometallurgy, 2026)

Effects of sorghum variety on fermentation microecology and flavor characteristics of sesame-flavor Baijiu - Guihu Zhang; Jiaxin Tang; Chunyan Liu; Linlin Liu; Deyi Zhao; Yansong Xue; Bei-Zhong Han (Food Research International, 2026)

Building damage-matched ground motion generation method using physics-guided generative adversarial networks - Qingle Cheng; Haotian Ren; Hongyu Zhao; Aiqun Li; Linlin Xie (Engineering Structures, 2026)

Ginsenoside Rk1 reprograms ‘cold’ cancer cell membranes into a ‘hot’ antigen repertoire for highly immunogenic cancer vaccines - Fangming Dong; Linlin Qu; Lebin Wang; Jing Zhao; Zhiguang Duan; Xueqing Yu; Xiaoxuan Ma; Daidi Fan (Chemical Engineering Journal, 2026)

Synergistic interaction between lead and cadmium via metal-transporter gene upregulation in mice - Tingting Zhang; Weiqin Xing; James A. Ippolito; Shuangshuang Shao; Xinjun Huang; Yongqiang Yang; Linlin Zhao; Yongxia Cheng; Liping Li (BioMetals, 2026)
This study investigated the potential synergistic interactions between Pb and Cd, and assessed the contribution of transporter gene expression to the synergism. Mice were administered varying doses of Pb (15, 30 and 108 mg kg −1 ) or Cd (1, 2 and 3 mg kg −1 ), or a combination of both in the feed. Liver, kidney and bone samples were analyzed for Cd, Pb, Cu, Mn, Zn and Fe concentrations. For treatments exhibiting synergistic effects, the relative expression levels of the divalent metal transporter 1 ( Dmt1 ), ZRT-IRE-like protein 8 ( Zip8 ) and Zip14 were quantified in the liver and kidney using Quantitative Real-Time Reverse Transcription Polymerase Chain Reaction (qRT-PCR). At 108 mg kg −1 Pb , increasing Cd doses from 0 to 1 mg kg −1 significantly increased Pb concentrations in the kidney, liver and bone by 10.6, 60.2 and 19.6%, respectively; concurrently, the relative expression of the Zip8 in the kidney increased by 69.5%, while Dmt1 and Zip14 expression in the liver increased by 79.0 and 85.6%, respectively. At Cd doses ≥ 1 mg kg −1 , increasing Pb rate resulted in elevated Cd concentrations in the kidney, liver and bone; however, no significant changes in transporter expression levels were observed in the kidney under these treatments, possibly due to the upregulation of transporter genes in the intestines. Results demonstrate that interactions between Pb and Cd can be synergistic, and upregulation of certain transporter genes were responsible for such synergism. These findings offer important insights for mitigating the health risks associated with heavy metal exposure in animal and humans.

A large rigid π-conjugated framework enables a single-component nanoparticle system for synergistic photothermal/photodynamic antibacterial therapy - Jialong Zhang; Zhuang Liu; Yuan Yu; Chenxi Li; Jing Wang; Linlin Zhao; Yan Lu (Chemical Engineering Journal, 2026)

Bithiophene-engineered carbon nitride with boosted built-in electric field and n-π* transition for PMS activation and 2,4-dichlorophenol degradation - Jihan Zhao; Zhihan Xue; Wei Jiang; Tianyu Zhou; Linlin Liu; Chunbo Liu (Environmental Research, 2026)

Atomic-level regulation of peroxymonosulfate activation on coal gangue: Toward controllable catalytic pathways and enhanced environmental resilience - Lixin Li; Peijiang Han; Tao Qin; Bo Zhang; Linlin Huang; Xue Dong; Qingju Tang; Xin Zhao; Fengxia Deng (Environmental Research, 2026)

Effect of coupled temperature-humidity drying on multi-scale structure and in vitro digestibility of corn resistant starch - Qing Su; Lirong Chen; Linlin Sun; Xingya Wang; Yuqiu Guo; Meimei Zhao; Kaichang Liu; Kuijie Gong (Food Chemistry, 2026)

Enzymatic synthesis of oligodextran with prebiotic potential by a recombinant dextransucrase from Latilactobacillus sakei L3 - Binbin Wang; Linlin Hao; Kaiyue Zuo; Xiaojing Liu; Huimin Yao; Weizhong Liu; Fangkun Zhao; Lei Pan; Baomei Wu (Carbohydrate Polymers, 2026)

Transforming waste derived phosphate sources into resources for fluoride immobilization by microbially induced phosphate precipitation - Linlin Cui; Jianxing Sun; Min Huang; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Bioresource Technology, 2026)

Understanding eco-hydrological processes in winter wheat croplands through physically consistent modelling - Linlin Li; Yunfei Wang; Aofan Cui; Xinyu Mao; Wenjun Zhao; Wei Li (Theoretical and Applied Climatology, 2026)

Engineering carbon dots with amplified peroxidase-mimetic activity for dual-modal colorimetric-photothermal sensing of organophosphorus and carbamate pesticides - Na Gao; Yajuan Zhao; Yuhan Huang; Yanke Zhou; Linlin Yang; Liguo Ji; Hao Zhu; Wenjie Ren; Guangjie He (Analytica Chimica Acta, 2026)

A bioinspired chitosan-polymer facilitated CO2 utilization under mild reaction conditions - Linlin Li; Jiang Zhao; Qingmei Ge; Yin-Hui Huang; Hang Cong; Wenfeng Zhao (Biomass and Bioenergy, 2026)

Genomic and functional characterization of a novel urease-producing bacterium Sulfitobacter sp. IGS-18 for simultaneous coal dust suppression and ammonia nitrogen removal during microbially induced calcite precipitation - Wen Nie; Ruoxi Li; Yue Zhao; Gang Li; Wenjin Niu; Qifan Tian; Jin Shi; Linlin Zhang (Journal of Environmental Chemical Engineering, 2026)

CLEC14A mediates trophoblast dysfunction in unexplained miscarriage by disrupting the cAMP/ERK signaling pathway - Jianing Wang; Yawei Shao; Linlin Zhou; Ruyue Ma; Shunli Dong; Ruiheng Zhao (Journal of Molecular Histology, 2026)

Rapid seismic response prediction method of regional buildings under mainshock-aftershock sequence based on deep learning - Qingle Cheng; Hongyu Zhao; Xiangchi Meng; Linlin Xie; Yuan Tian (Bulletin of Earthquake Engineering, 2026)

Linking genetic connectivity and ecological niche similarity to inform coastal biosecurity management: a global case study of Mytilopsis sallei - Hao Dong; Linlin Zhao; Liuyi Huang; Xiaoyang Wang; Changdong Liu (Ocean & Coastal Management, 2026)

Extraction of tungsten and molybdenum from low-grade tungsten-molybdenum ore: Thermodynamic calculations and kinetic analyses - Jian Kang; Linlin Tong; Qin Zhang; Zhenan Jin; Han Zhao; Bin Xiong; Hongying Yang (Minerals Engineering, 2026)

Pore-expanded core-shell adsorbent for high Cu(II) adsorption: Performance and DFT mechanism - Yintao Li; Jianwen Wei; Linlin Geng; Dongling Zhao; Xiaobin Zhou (Journal of Water Process Engineering, 2026)

Paleozoic polyphase strain and rheological evolution of the Shangdan shear zone, Qinling Orogen, central China - Linlin Zeng; Han Zheng; Ian P. Cawood; Dexian Zhang; Shibo Han; Peixuan Kang; Guochun Zhao (Journal of Structural Geology, 2026)

Effects of combined selenium and sulfur application on glucosinolate biosynthesis in Chinese cabbage sprouts - Huixia Bai; Linlin Zhao; Yafang Luo; Qi Hu; Lingling Liu; Yang Chen; Huan Wang; Yushu Wang (Physiology and Molecular Biology of Plants, 2026)

Nanopore-Based Full-Length Transcriptome Sequencing: In-Depth Exploration of Green Sea Turtle (Chelonia mydas) Genome - Qi Huang; Yongjun Sun; Linlin Zhao; Wenbo Zhu; Fei Shao; Jin Xu; Yongjian Qin (Fishes, 2026)
The green sea turtle (Chelonia mydas), a widely distributed species, plays a crucial role in maintaining the marine ecosystem. However, studies on C. mydas require accurate and comprehensive genome annotation information. Long-read direct transcriptome data of C. mydas were obtained using direct RNA sequencing on the Oxford Nanopore Technologies (ONT) platform from blood tissue of a single captive individual. A total of 4061 novel transcripts were obtained by comparing long-read direct transcripts with genome annotation of C. mydas. We also predicted 2402 CDSs on the novel transcripts. Among them, 1208 (50.29%) had functional annotation information in the databases. In addition, we predicted and analyzed AS events, fusion transcripts, methylation sites, poly(A)s, and lncRNAs in the C. mydas long-read direct transcriptome. Overall, our study provides the a long-read direct blood transcriptome for C. mydas to complement and improve its genome annotation. This valuable resource will contribute to future research on C. mydas. Additionally, the analyses of transcriptome structure mentioned above may provide new insights and ideas for the study of C. mydas.

Spatiotemporal distribution, source apportionment, and ecological risks of polycyclic aromatic hydrocarbons in surface water of the Southern Ocean - Tao Yang; Linlin Shi; Saizhang Tan; Bangping Deng; Yu Ke; Shengming Cheng; Yubin Li; Shuangcheng Zhang; Jingwei Wu; Lichen Zhao; Jun Shi (Frontiers in Marine Science, 2026)
In Antarctica, low temperatures favor the trapping and deposition of polycyclic aromatic hydrocarbons (PAHs), whereas the biogeochemical cycling of PAHs on the Southern Ocean adjacent to Antarctica is highly sensitive to climate change. However, very little environmental and ecological information is available on interannual PAHs variations in the surface of the Southern Ocean. From 2022 to 2024, we employed the 38 th , 39 th , and 40 th Chinese National Antarctic Research Expeditions (CHINARE) to collect surface water samples and conduct analyses of the spatio-temporal distribution patterns, source apportionment, and probabilistic ecological risk assessment of the 16 USEPA priority PAHs. We found that ∑PAH concentration in the study area ranged from 427 to 5782 pg/L, with median values of 1795, 1736, and 2559 pg/L for the 38 th , 39 th , and 40 th expeditions, respectively, showing a latitudinal gradient pattern of higher concentrations at lower latitudes and lower concentrations at higher latitudes. A significant concentration rebound was observed in the 40th expedition. Integrated analysis using molecular diagnostic ratios, PCA, and PMF revealed that this rebound was driven by a distinct “dual-pressure pattern”: intensified logistical traffic emissions (combustion sources) and the persistent release of fresh, unweathered PAHs. Source apportionment indicated an evolutionary trend from mixed petrogenic and ship-related liquid fuel combustion (38th) to episodic fresh local inputs (39th), culminating in the complex superposition of sources in the 40th survey. Probabilistic risk assessment using Monte Carlo simulations confirmed that acute risks to plankton remain low (the 95th percentile of ∑RQ MPC was 0.077); However, a structural shift towards hydrophobic high-molecular-weight PAHs (increasing to ~18% in 2024) signals a rising hidden potential for biomagnification in keystone species like Euphausia superba . These findings provide a critical scientific baseline for identifying pollution sources and supporting Antarctic ecosystem management under changing environmental conditions.

Carbon dots/konjac glucomannan/starch anti-freezing gel: development and cryoprotective coating for beef preservation - Linlin Zhao; Zeyue Zhao; Wenqin Gu; Huinan Jiang; Hao Xu; Suqing Sun; Xiangren Meng (Food Research International, 2026)

Seven neonicotinoids and twenty-two metabolites in seven food matrices by optimized QuEChERS-HPLC-MS/MS and dietary risk assessment - Zhenzhen Zhou; Xueyan Zhao; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie; Fajun Tian (Food Chemistry, 2026)

Soil bacterial community assembly and driving factors in wetlands along the southern margin of the Tarim Basin - Linlin Zhang; Peishan Zhao; Guanglei Gao; Guodong Ding; Ying Zhang; Qiyan Li; Yilin Liu (Applied Soil Ecology, 2026)

Oleogels in flour-based foods: an overview from the perspective of crystalline structure and functional performance - Yi Han; Linlin Li; Lukai Ma; Jingyuan Su; Yang Zhao; Jian Zhang; Yanxia An (Food Chemistry, 2026)

A high-order Model-free Dynamic Framework for Accurate Daily Streamflow Prediction - Jiaying Zhang; Shiqian Tang; Longxia Qian; Mei Hong; Yong Zhao; Linlin Fan (Water Resources Management, 2026)

Intelligent Recognition Network for Difficult Airway Based on Multi-View Input and Attention Aggregation - Fan Zhang; Jiaqiang Zhang; Zhaoxiang Zhang; Ke Yang; Linlin Zhao; Yuelei Xu (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Analysis of recovery-related white matter microstructures in visual spatial neglect based on diffusion tensor imaging - Linlin Ye; Wanying Zhao; Weiqun Song; Huaqing Yang; Huanxin Xie; Lei Cao (Brain Imaging and Behavior, 2026)

A Deep-Sea Multi-Sequence Sampling System Integrating In Situ Microbial Filtration with Rapid RNA Stabilization - Wei Bu; Yuan-Jie Chen; Jinhai Luo; Linlin Sun; Xiang Li; Xinyuan Gao; Yuanli Fang; Leisheng Tang; Jiaying Zhao; Jingchun Feng; Haocai Huang (Journal of Marine Science and Engineering, 2026)
Rapid depressurization and warming during recovery can trigger stress in deep-sea microbes and accelerate RNA degradation. We developed a remotely operated vehicle (ROV)-oriented multi-sequence microbial sampler for 2000 m sampling (20 MPa, 2 °C) that integrates in situ filtration with immediate RNAlater injection (an RNA stabilization reagent), collecting up to 12 samples per dive. A Dirichlet sampling–B-spline–SVM framework was used to optimize the cam profile of the sequence trigger for robust actuation under geometric constraints and realistic tolerances in both manufacturing and assembly. Relative to the baseline 3-4-5 motion law, the optimized design reduces nominal peak driving torque by ~18–20% and lowers the maximum torque under tolerance perturbations; tests show a further ~10–25% reduction using a SiC ball–ZrO2 block pair versus a MoS2-lubricated titanium pushrod–ZrO2 block pair. A Darcy–Forchheimer porous-media computational fluid dynamics (CFD) model predicts earlier clogging on the lower membrane and a fast-to-slow RNAlater displacement process; greater membrane resistance mismatch delays 95% displacement and increases RNAlater loss. Simulations and Rhodamine B tests suggest an RNAlater consumption of 0.9 L per parallel filter (one membrane per side), and 20 MPa chamber tests confirm stable operation and membrane retrieval.

Insights into low temperature adaptation in Epinephelus awoara through integrated genome and transcriptome analysis - Linna Wang; Shuai Chen; Zhentong Li; Yang Liu; Shihao Wang; Tangtang Ding; Fengfan Yang; Chunbai Zhang; Linlin Li; Wensheng Li; Qingbin Wang; Xia Zhao; et al. (Aquaculture, 2026)

Research on forecasting and analysis methods for ship deck icing in polar regions - Zhenze Yang; Zhenju Chuang; Linlin Yin; Yijie Zhao; Nan Gao (Ocean Engineering, 2026)

Oxygen vacancy induced strong interaction of single atom Ru with In2O3 for improved CO2 hydrogenation to methanol - Shilong Xiong; Song He; Linlin Wu; Haibo Zhao; Chang-jun Liu (Chemical Engineering Journal, 2026)

Juvenile-Onset Cerebrotendinous Xanthomatosis with Novel Compound Heterozygous CYP27A1 Mutations: Case Series and Literature Review - Kefang Du; Chunrong Wang; Linlin Wan; Zhao Chen; Hongyu Yuan; Qian Jiang; Xiao Dong; Daji Chen; Riwei Ouyang; Xiafei Long; Xiaokang Wu; Xinying Xiao; et al. (The Cerebellum, 2026)

Synergistic DFT and experimental design of Ga/W Co-Doped SnS2 microspheres with enriched sulfur vacancies for enhanced NO2 sensing - Wei Zhao; Lanlan Guo; Xin Shi; Linlin Dong; Yingli Yang; Xueli Yang; Xiaolian Liu; Guodong Wang; Yan Wang (Chemical Engineering Journal, 2026)

Deciphering Ferroptosis-Related Astrocyte Subpopulations and Diagnostic Biomarkers in Parkinson’s Disease through RNA Transcriptomics - Zhongying Gong; Dan Guo; Yufeng Lin; Zhiwei Liu; Mengdi Lv; Xinxin Liu; Mingshuo Sun; Linlin Wang; Tianman Zhao; Zhiyun Wang; Xue Xue (Molecular Neurobiology, 2026)

Curvature sensing strategy for flexible gripper fingers during grasping deformation: enabling in-orchard online apple size grading - Guangze Zhao; Hongjian Zhang; Jingwei Sun; Huawei Yang; Shaowei Wang; Shuangxi Liu; Xinpeng Cao; Shenghui Fu; Yongxian Wang; Linlin Sun; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Synergistic extraction of molybdenum and tungsten from low-grade tungsten-molybdenum ores with poor flotation separability using a sodium hypochlorite-trisodium phosphate-sodium hydroxide system - Jian Kang; Linlin Tong; Qin Zhang; Han Zhao; Bin Xiong; Hongying Yang (Minerals Engineering, 2025)

Mitigating iron contamination in cyanide gold extraction: Ceramic grinding media for enhanced efficiency and reduced cyanide consumption - Qianfei Zhao; Yuhai Zhang; Peng Gao; Linlin Tong; Yuexin Han; Hongying Yang; Shuai Yuan (Minerals Engineering, 2025)

The role of water regime in soil organic carbon preservation in mangrove wetlands: “iron gate” vs. “enzyme latch” - Haixiao Zhao; Zhengang Wang; Wei Yang; Linlin Yao; Qian Tan (Journal of Hydrology, 2025)

Filamentous cyanobacterium Spirulina platensis mediates phosphate biomineralization for efficient fluoride immobilization and drives metabolic shift toward stress resistance and biomineralization - Linlin Cui; Zhilian Liu; Jun Suo; Yun Liu; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Journal of Hazardous Materials, 2025)

A transformer-based deep learning approach for mechanical response prediction and failure analysis of precast bridge slab joints using strain field - Qiliang Zhao; Weijian Zhao; Linlin Yuan; Ruoshui Xing; Bochao Sun; Yuanzhang Yang (Engineering Structures, 2025)

Mitochondria-targeted nanoparticles with whole-course-repair efficacy in therapy of myocardial ischemia reperfusion injury - Xiya Wang; Hang Chen; Pingyuan Sun; Linlin Zhao; Renxiang Gui; Xu Wang; Emeli Chatterjee; Jiahong Xu; Jianle Chen; Xuerui Chen (Chemical Engineering Journal, 2025)

Construction of temperature-responsive helical carbon nanofibers-based composites toward switchable microwave absorption - Yudi Li; Linlin Zhao; Wei Feng; Rongling Zhang; Xialong Cai; Zhiyong Chen; Hanjun Wei; Xulin Yang; Pan Wang; Giulio Cerullo; Nabil Kadhim Taieh; Fanbin Meng; et al. (Chemical Engineering Journal, 2025)

OWTDNet: A Novel CNN-Mamba Fusion Network for Offshore Wind Turbine Detection in High-Resolution Remote Sensing Images - Pengcheng Sha; Sujie Lu; Zongjie Xu; Jianhai Yu; Lei Li; Yibo Zou; Linlin Zhao (Journal of Marine Science and Engineering, 2025)
Real-time monitoring of offshore wind turbines (OWTs) through satellite remote sensing imagery is considered an essential process for large-scale infrastructure surveillance in ocean engineering. Current detection systems, however, are constrained by persistent technical limitations, including prohibitive deployment costs, insufficient discriminative power for learned features, and susceptibility to environmental interference. To address these challenges, a dual-branch architecture named OWTDNet is proposed, which integrates global contextual modeling via State Space Models (SSMs) with CNN-based local feature extraction for high-resolution OWTs detection. The primary branch utilizes a Mamba-structured encoder with linear computational complexity to establish long-range spatial dependencies, while an auxiliary Blurring-MobileNetv3 (B-Mv3) branch is designed to compensate for the local feature extraction deficiencies inherent in SSMs. Additionally, a novel Feature Alignment Module (FAM) is introduced to systematically coordinate cross-modal feature fusion between Mamba and CNN branches through channel-wise recalibration and position-aware alignment mechanisms. This module not only enables complementary feature integration but also enhances turbine-specific responses through attention-driven feature modulation. Comprehensive experimental validation demonstrated the superiority of the proposed framework, achieving a mean average precision (AP) of 47.1% on 40,000 × 40,000-pixel satellite imagery, while maintaining practical computational efficiency (127.7 s per image processing time).

Does soil compaction affect the mobility and transformation behavior of Arsenic -A case study of an Alfisol - Xinjun Huang; Lanting Liu; Yali Wang; Yongqiang Yang; Linlin Zhao; Rainer Horn; Liping Li (Soil and Tillage Research, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Investigating the aroma transition during rapid mango ripening driven by dynamic catabolism of fatty acids - Yuanping Wang; Zhenjiang Zhou; Yonghao Liu; Rongli Pang; Xi Zhao; Qi Chen; Linlin Guo; Baiyi Lu (Food Chemistry, 2025)

Consumption of fermented Cd and Pb contaminated wheat flour increases potential health risk - Weiqin Xing; Zhexu Si; James A. Ippolito; Guobing Lin; Farzana Kastury; Sen Ma; Kunyan Qiu; Linlin Zhao; Lena Q. Ma; Liping Li (Food and Chemical Toxicology, 2025)

Salvianolic Acid B and Ginsenoside Rg1 Combination Attenuates Cerebral Edema Accompanying Glymphatic Modulation - Lingxiao Zhang; Yanan Shao; Zhao Fang; Siqi Chen; Yixuan Wang; Han Sha; Yuhan Zhang; Linlin Wang; Yi Jin; Hao Chen; Baohong Jiang (Neuroscience Bulletin, 2025)

Relationship of Interhemispheric Signal Propagation and Severity of Stroke-induced Damage and Unilateral Neglect: A Retrospective Study - Wanying Zhao; Huanxin Xie; Weiqun Song; Lei Cao; Linlin Ye (Brain Topography, 2025)

Triboelectric force feedback-based fully actuated adaptive apple-picking gripper for optimized stability and non-destructive harvesting - Jingwei Sun; Linlin Sun; Guangze Zhao; Junsheng Liu; Zixu Chen; Linlong Jing; Xinpeng Cao; Hongjian Zhang; Wei Tang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Predicting seasonal distribution and inter-seasonal migration corridors for three subspecies of common minke whales - Linjie Li; Linlin Zhao; Shiji Xu; Changdong Liu; Yanli Tang (Ocean & Coastal Management, 2025)

Spatial planning for dugong conservation: Assessing habitat suitability and conservation gaps in Indo-Pacific Convergence Zone - Bei Wang; Kaiyu Liu; Watchara Sakornwimon; Wenhao Huang; Tingting Li; Xianshui Lai; Chengcheng Li; Linlin Zhao; Bailin Cong; Shenghao Liu (Marine Policy, 2025)

Recent progress in hygroscopicity improvement strategies of protein-based films for edible food packaging - Yiyi Chen; Xiangren Meng; Linlin Zhao; Pei Peng; Ying Ma; Jing Wang (Trends in Food Science & Technology, 2025)

Experimental investigation on local scour around a cubic artificial reef in bidirectional tidal currents - Linlin Wang; Mingda Yang; Muk Chen Ong; Fenfang Zhao; Yujie Cui; Yanli Tang (Ocean Engineering, 2025)

Rb-Sr dating of pyrite, Zircon U-Pb geochronology, and Sr-Nd-Hf isotopic geochemistry of the Baiyun Au deposit in the Qingchengzi Orefield, Liaodong Peninsula, Northeast China - Peng Zhang; Junchao Lü; Yan Zhao; Linlin Kou; Wei Pang (Journal of Geochemical Exploration, 2025)

Boosting dynamic NH3 adsorption performance of UiO-66 via amino-induced local polarization - Zimu Liu; Mingtai Li; Zitong Zhao; Yulong Yang; Linlin Deng; Baojuan Dou; Feng Bin (Journal of Environmental Chemical Engineering, 2025)

Simultaneous fluoride, calcium, and phosphorus removal by bacterial phosphate mineralization: Reaction pathways, mechanisms, and process optimization - Linlin Cui; Zhilian Liu; Jun Suo; Jue Kang; Yun Liu; Guanzhou Qiu; Hongbo Zhao; Li Shen (Journal of Environmental Chemical Engineering, 2025)

Enhanced selective oxidation of 5-Hydroxymethylfurfural with a recyclable V34@Fe3O4/C catalyst Enriched with Mixed-valence polyoxovanadate active centers - Chunhui Zhang; Mengqi Wang; Changhao Zhao; Junpeng Wang; Yundong Cao; Linlin Fan; Hong Liu; Guang-Gang Gao (Fuel, 2025)

Molecular and physiological adaptations of Scartelaos histophorus to air exposure: Implications for amphibious fish survival - Dongdong Xiao; Ruizhi Wang; Peidong Zhang; Riyanti; Linlin Zhao; Na Song (Environmental Research, 2025)

Microseismic criterion for dynamic risk assessment and warning of roadway rockburst induced by coal mine seismicity - Lianpeng Dai; Xin Zhao; Yishan Pan; Hao Luo; Yanan Gao; Aiwen Wang; Linlin Ding; Peng Li (Engineering Geology, 2025)

Deep learning for wildfire risk prediction: Integrating remote sensing and environmental data - Zhengsen Xu; Jonathan Li; Sibo Cheng; Xue Rui; Yu Zhao; Hongjie He; Haiyan Guan; Aryan Sharma; Matthew Erxleben; Ryan Chang; Lincoln Linlin Xu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

CRISPR/Cas9-mediated promoterless gene targeting reduces lysosome storage in MPS VII mice - Linlin Shan; Qiongyan He; Weifeng Zhang; Xiaojing Zheng; Junli Zhao; Peiyan Yang; Qinwen Mao; Haibin Xia (Science China Life Sciences, 2025)

Effects of Land-Use Change on Soil Infiltrability and Preferential Flow in Typical Low Hilly Area - Linlin Chu; Rong Ma; Yue Liu; Yan Zhao; Lidong Bi; Chen Dan (Journal of Soil Science and Plant Nutrition, 2025)

Extending the Mutational Spectrum of SYNE1 Ataxia in Chinese Patients - Xin Huang; Zhao Chen; Qian Jiang; Panyan Liu; Yiqing Gong; Lijing Lei; Jia Chen; Chunrong Wang; Linlin Wan; Lang He; Linliu Peng; Rong Qiu; et al. (The Cerebellum, 2025)

Coupled precipitation enrichment of molybdenum and tungsten for synthesizing AMTOF (artificial molybdenum and tungsten ore first) from a complex trace molybdenum-tungsten mixed solution - Han Zhao; Hongying Yang; Linlin Tong; Qin Zhang; Jiapeng Zhang (Minerals Engineering, 2025)

SIMPLE: A One-Pot RPA-Cas12b Method for Single Nucleotide Variations Identification with an Expanded Scope and Clinical Applications - Kaiming Guo; Yongkang Lai; Yiru Han; Linlin Bai; Ting Wang; Shengzhou Wang; Ziqin Zhang; Dianwei Liu; Yanju Chen; Jiulong Zhao; Yanan Pang; Feng Qian; et al. (Phenomics, 2025)

Monitoring of Larch Caterpillar (Dendrolimus superans) Infestation Dynamics Using Time-series Sentinel Images in Changbai Mountains National Nature Reserve, Northeast China - Linlin Wu; Mingchang Wang; Jiatao Du; Jingzheng Zhao; Fengyan Wang (Chinese Geographical Science, 2025)

Impacts of spatial resolutions of UAV-LiDAR-derived DEMs on erosion modelling in the hilly and gully Loess Plateau - Wenli Li; Pengfei Li; Lu Yan; Jinfei Hu; Leiqin Wang; Dou Li; Yang Dan; Linlin Huang; Guangju Zhao (CATENA, 2025)

Distribution of glucosinolates and antioxidants in different leaf-layers of Kale (Brassica oleracea var. acephala DC.) - Yafang Luo; Huixia Bai; Linlin Zhao; Qi Hu; Xinyuan Li; Zhenyu Fan; Yushu Wang (Physiology and Molecular Biology of Plants, 2025)

Identification of autophagy-related biomarkers in prostate cancer prognosis - Yancheng Di; Linlin Zhao; Lingling Zhang; Lei Chen (Human Cell, 2025)

An automated river shoreline space type identification method using remote sensing data that considers space-channel attention multi-scale features - Shijiao Qiao; Wanlai Xue; Kun Jia; Jie Li; Mu Xia; Zhulin Chen; Haiying Jiang; Bo Yuan; Guofeng Tao; Yuran Cui; Linlin Zhao; Zihang Jiang; et al. (International Journal of Remote Sensing, 2025)

Global variations of urban form: Characterization and quantification through intelligent remote sensing image analysis - Jie Chen; Geng Sun; Yongze Song; Yinxia Cao; Cheolhee Yoo; Ya Guo; Chunhong Zhao; Linlin Lu; Qihao Weng (Sustainable Cities and Society, 2025)

A coupled model of nonlinear dynamical system and deep learning for multi-step ahead daily runoff prediction for data scarce regions - Longxia Qian; Wei Hu; Yong Zhao; Mei Hong; Linlin Fan (Journal of Hydrology, 2025)

Lactobacillus plantarum reduces polystyrene microplastic induced toxicity via multiple pathways: A potentially effective and safe dietary strategy to counteract microplastic harm - Liuting Shi; Changyin Wu; Yuye Wang; Linlin Wang; Peijun Tian; Ke-xin Shang; Jianxin Zhao; Gang Wang (Journal of Hazardous Materials, 2025)

One-step synthesis of K3PO4-activated phosphorus-enriched carbons for enhanced carbon capture - Yue Zhi; Yujia Yin; Quji Ciren; Qiang Xiao; Leihong Zhao; Muslum Demir; Utku Bulut Simsek; Xin Hu; Linlin Wang (Journal of Environmental Chemical Engineering, 2025)

Phospholipids and phosphoprotein-encapsulated silver nanoparticles: An eco-friendly and green antibacterial agent for killing bacteria and promoting chronic wound healing - Qian Cai; Wenting Chen; Haoying Zhang; Chuyu Tang; Songjing Zhong; Qinyu Zhao; Zhuo Wang; Chao Wu; Liugen Zheng; Yuanyuan Cheng; Linlin Li (Journal of Environmental Chemical Engineering, 2025)

Promoting oxidation of high concentration CO via strong metal support interaction in unreduced Pt-based catalysts - Yulong Yang; Xiaokun Yi; Linlin Deng; Zitong Zhao; Zimu Liu; Mingtai Li; Baojuan Dou; Feng Bin (Journal of Environmental Chemical Engineering, 2025)

Licorice water extract improves constipation by repairing the intestinal barrier and regulating the gut microbiota: A potential alternative treatment strategy - Mingwei Sun; Meng Zhao; Linlin Du; Jieying Hou; Juane Dong; Bin Zhang (Food Bioscience, 2025)

Tendon injury repair strategy driven by supramolecular hydrogen bonding and dynamic covalent bond self-assembly microspheres - Taishan Liu; Xiaoxuan Ma; Chenhui Zhu; Yu Mi; Jing Zhao; Linlin Qu; Huan Lei; Daidi Fan (Chemical Engineering Journal, 2025)

Polysaccharides from traditional Chinese medicine and their nano-formulated delivery systems for cancer immunotherapy - Linlin Sun; Yuting Liu; Qihui Sun; Guimei Wang; Baoxiang Du; Bodong Liu; Tian Gao; Pan Zhao; Yong Yang; Rong Rong (Carbohydrate Polymers, 2025)

Climate evolution and its driving factors in the Tethys Sea region during the Cenozoic - Jiangbo Meng; Jiagang Zhao; Linlin Chen; Paul J. Valdes; Alex Farnsworth; Svetlana Popova; Mine Sezgül Kayseri-Özer; Gaurav Srivastava; Jian Huang; Tao Su; Zhekun Zhou; Shufeng Li (Science China Earth Sciences, 2025)

Exploring Neurobiological Effects of Intermittent Theta-Burst Stimulation on the Left Cerebellum for Post-stroke Unilateral Neglect: A Preliminary Transcranial Magnetic Stimulation—Electroencephalography Investigation - Linlin Ye; Wanying Zhao; Yichen Zhang; Weiqun Song; Huanxin Xie; Lei Cao (The Cerebellum, 2025)

Prediction of landfill gases concentration based on Grey Wolf Optimization – Support Vector Regression during landfill excavation process - Zhansheng Liu; Zehua Zhang; Qingwen Zhang; Linlin Zhao (Waste Management, 2025)

Changes in intergranular air properties and fatty acid profile of wheat bulk in a large warehouse with air-conditioned oversummering - Mengya Wang; Minghui Zhao; Xuhui Zhuang; Jianzhang Wu; Xingjun Li; Linlin Song; Yushan Jiang (Journal of Stored Products Research, 2025)

Optimized immobilization of lead and cadmium in soil using dithiocarboxy functionalized silica: A long-term effectiveness study - Mingming Lian; Chaoran Li; Longfei Wang; Liyong Niu; Linlin Zhao; Dongdong Wu; Zongsheng Zhao; Xiaohong Li; Zhijun Zhang (Journal of Hazardous Materials, 2025)

Development of a colorimetric sensor array with weighted RGB strategy for quality differentiation of Anji white tea - Qilin Xu; Xianggang Yin; Xinyi Huo; Xiaohan Zhao; Linlin Wu; Yifeng Zhou; Jun Huang (Journal of Food Engineering, 2025)

Planning conservation priority areas for marine mammals accounting for human impact, climate change and multidimensionality of biodiversity - Linjie Li; Yanli Tang; Hao Dong; Linlin Zhao; Changdong Liu (Journal of Environmental Management, 2025)

Studying the Impact of the Load Distribution Ratio on the Unsteady Performance of a Dual-Stage Pump-Jet Propulsor - Jiansheng Zhang; Ning Liang; Jianwei Zhang; Linlin Cao; Dazhuan Wu; Wei Zhao; Hanqiao Han (Journal of Marine Science and Engineering, 2025)
This study investigated the impact of different load distribution ratios between two rotors on the unsteady performance of dual-stage pump-jet propulsors using Computational Fluid Dynamics (CFDs) and experimental methods. The Shear Stress Transport (SST) k-ω model was employed to solve turbulence problems, and the numerical simulation method used was validated. The following conclusions were drawn: Different load distribution ratios of the dual-stage rotors have no significant impact on the overall propulsion performance of the propulsor. As the load distribution ratio is aft-shifted, the axial unsteady force of the entire propulsor continuously decreases, with a reduction of up to 53.6%. This is due to the gradual reduction in the energy of the first-stage rotor, leading to a more uniform Blade-Passing Frequency Velocity Harmonic Coefficient (BPFVHC) in front of the second-stage rotor, thereby gradually reducing the unsteady force of the second-stage rotor. The experimental results also indicate that the aft-shifted load model can reduce the sound pressure level of the propulsor. Compared to the prototype propulsor, the sound pressure level at the Blade-Passing Frequency decreases by 6.67 dB, or about 78.5%, in sound energy. This study has important implications for the low-excitation design of dual-stage pump-jet propulsors.

Tanshinone IIA@β-cyclodextrin encapsulated with Eucommia ulmoides rubber/acetylated starch film as novel oral delivery system for therapy of orthotopic colon cancer - Rui Zhao; Haoyu Wang; Shuyao Li; Lingling Wang; Xiaopeng Lei; Pai Peng; Linlin Du; Juane Dong (Carbohydrate Polymers, 2025)

Influence of ocean-atmosphere interactions on typhoon track and intensity: a case study for typhoon “Hato” (1713) - Yonghang Chen; Yu Wei; Yunxia Zheng; Xianwen Wu; Qiong Liu; Ruixue Li; Linlin Sun; Bingke Zhao; Sijie Yin; Haicheng Liu; Xiaoyu Li (Natural Hazards, 2025)

Association of Urinary Phthalate Metabolites with Lipid Profiles and the Mediating Role of Serum Globulin: A Repeated-Measures Study - Kun Huang; Linlin Liu; Lei Zhao; Miao Liu; Chongjian Wang; Wenting Guo; Huihua Yang; Rui Zhu; Xiaomin Zhang (Exposure and Health, 2025)

An enhanced machine learning model for urban air quality forecasting under intense human activities - Yelin Wang; Feiyang Xia; Linlin Yao; Shunyu Zhao; Youjie Li; Yanpeng Cai (Urban Climate, 2025)

Novel NIR-Ⅱ-Activated titanate-supported iridium nanoplatform delivers multimodal antitumor therapy synergistic with PD-1 inhibition in TNBC - Peixin Du; Xian Jiang; Zihan Xu; Linlin Song; Meixu Chen; Yujie Zhao; Jing Yu; Tianyue Xu; Ting Sun; Huang Zhu; Hubing Shi; Jing Jing (Chemical Engineering Journal, 2025)

Butyrylated modification of corn starch alleviates autism-like behaviors by modulating 5-hydroxytryptamine metabolism and gut-brain neural activity - Wentian Li; Qingmin Kong; Min Guo; Linlin Wang; Peijun Tian; Jingyu Lu; Jianxin Zhao; Wei Chen; Gang Wang (Carbohydrate Polymers, 2025)

Effects of cadmium (Cd) on photosynthetic characteristics and chlorophyll fluorescence parameters in the ornamental Plant Salvia splendens Ker-Gawl - Lian Jia; Guangchao Yu; Zhen Zhao; LinLin Lü (Physiology and Molecular Biology of Plants, 2025)

A dual deep learning approach for winter temperature prediction in solar greenhouses in Northern China - Jingxin Yu; Jinpeng Zhao; Congcong Sun; Ruochen Zhang; Wengang Zheng; Linlin Xu; Xiaoming Wei (Computers and Electronics in Agriculture, 2025)

Experimental and numerical investigation of flow field characteristics and local scour around trapezoidal artificial reefs - Mingda Yang; Yanli Tang; Linlin Wang; Fenfang Zhao; Shuyue He (Ocean Engineering, 2025)

Bacterial community composition and metabolic characteristics of three representative marine areas in northern China - Huameng Ge; Chengcheng Li; Conghui Huang; Linlin Zhao; Bailin Cong; Shenghao Liu (Marine Environmental Research, 2025)

Influence of atomic coordination on the activity of lattice oxygen and catalytic oxidation of toluene over regular Cu2O crystalline - Linlin Deng; Mingtai Li; Xin Gao; Xiaokun Yi; Yang Zhao; Yulong Yang; Zitong Zhao; Jiarui Chen; Baojuan Dou; Feng Bin (Journal of Hazardous Materials, 2025)

The role of telomere shortening in ambient ozone exposure-related insulin resistance - Ruiying Li; Gongbo Chen; Wei Liao; Yinghao Yuchi; Xiaohuan Yang; Ziyuan Zhang; Xiaotian Liu; Zhenxing Mao; Linlin Li; Jiahui Zhao; Huijun Li; Wenqian Huo; et al. (Journal of Hazardous Materials, 2025)

Failure and post-failure kinematic disaster processes of columnar rock masses based on 3D discontinuous deformation analysis - Ke Ma; Shengze Zhao; Guoyang Liu; Jianbin Miao; Jiashuo Kang; Linlin Wang; Qun Yu (International Journal of Rock Mechanics and Mining Sciences, 2025)

Lactic acid bacteria reduce polystyrene micro- and nanoplastics-induced toxicity through their bio-binding capacity and gut environment repair ability - Liuting Shi; Xin Teng; Changyin Wu; Tengxun Zhang; Xing Jin; Linlin Wang; Peijun Tian; Ke-xin Shang; Jianxin Zhao; Chitong Rao; Gang Wang (Environmental Pollution, 2025)

Chromosome-Level Genome Assembly and Comparative Genomic Analysis of Planiliza haematocheilus: Insights into Environmental Adaptation and Hypoxia Tolerance Mechanisms - Ruizhi Wang; Na Song; Linlin Zhao (Marine Biotechnology, 2025)

Effect of Feeding Mice Soluble Metals and Heavy Metal Contaminated Soil on Feces Metal Concentrations - Ningning Xu; Liping Li; James A. Ippolito; Weiqin Xing; Yale Wang; Baozhong Zhang; Yongqiang Yang; Ling Bai; Linlin Zhao (Biological Trace Element Research, 2025)

Salmonella enterica serovar typhimurium effectors spiA and spiC promote replication by modulating iron metabolism and oxidative stress - Keyuan Chen; Jing Wang; Ting Hu; Yiqing Zhao; Yi Wu; Xue Wang; Wei Li; Guiyan Yang; Linlin Zhang; Jiufeng Wang; Yaohong Zhu (Veterinary Microbiology, 2025)

Global distribution pattern and conservation of the cosmopolitan cold-water coral species Desmophyllum dianthus under climate change - Wenhao Huang; Zongling Wang; Fangyuan Qu; Chang Zhao; Miaozhuang Zheng; Zhaohui Zhang; Shenghao Liu; Qinzeng Xu; Xuelei Zhang; Linlin Zhao (Journal of Environmental Management, 2025)

Stability and sensory quality of plant-based milk substitutes made from 36 different oat varieties: Relation with oat kernels attributes - Lulu Cui; Jiani Zhao; Linlin Fan; Aijinxiu Ma; Fang Zhong; Sumei Zhou; Dianzhi Hou (Journal of Cereal Science, 2025)

Variations on the Thrifty Food Plan: Model diets that satisfy cost and nutrition constraints - Yiwen Zhao; Linlin Fan; Norbert L.W. Wilson; Angélica Valdés Valderrama; Parke Wilde (Food Policy, 2025)

2D manganese-doped calcium carbonate nanosheets as activable MRI/US imaging Guided enhanced calcium influx for Boosted regulatory cell death - Mingya Tan; Linlin Huo; Jie Zeng; Shiqi Zhu; Jianfeng Bao; Mengke Fan; Jiangyang Li; Meiling Liu; Jiayi Zhao; Zhenghuan Zhao (Chemical Engineering Journal, 2025)

BDNF-VGF Pathway Aggravates Incision Induced Acute Postoperative Pain via Upregulating the Neuroinflammation in Dorsal Root Ganglia - Wenjing Zhao; Lulin Ma; Daling Deng; Linlin Han; Feng Xu; Tianhao Zhang; Yafeng Wang; Shiqian Huang; Yuanyuan Ding; Shaofang Shu; Xiangdong Chen (Molecular Neurobiology, 2025)

An Improved Anticipated Learning Machine for Daily Runoff Prediction in Data-Scarce Regions - Wei Hu; Longxia Qian; Mei Hong; Yong Zhao; Linlin Fan (Mathematical Geosciences, 2025)

A comparative study on the toxic effects of lead pollution and nanoplastic-lead mixed pollution on red drum and their detoxification strategies - Zhicheng Sun; Linlin Zhao; Xin Peng; Bin Kang (Journal of Hazardous Materials, 2024)

The role of probiotics in the treatment of non-alcoholic fatty liver disease (NAFLD): New insights based on meta-analysis and subgroup analysis - Rui Xiao; Yang Cao; Linlin Wang; Peijun Tian; Qixiao Zhai; Jianxin Zhao; Gang Wang; Yu Zhu (Food Bioscience, 2024)

Low level exposure to BDE-47 facilitates the development of prostate cancer through TOP2A/LDHA/lactylation positive feedback circuit - Linlin Tian; Nan Zhou; Ning Zhao; Mengkai Qiao; Min He; Ziqing Mao; Wenjiong Xu; Dandan Xu; Yan Wang; Yan Xu; Tong Chen (Environmental Research, 2024)

Precise fabrication and superior combustion properties of n-B pomegranate microspheres based on a new dissolution-dispersion-coating method - Yushu Xiong; Baoxuan Li; Yinghong Wang; Linlin Liu; Jie Huang; Suhang Chen; Fengqi Zhao; Kangzhen Xu (Chemical Engineering Journal, 2024)

Umbrella effect of spotted seal conservation and achieving 30 × 30 targets in the Yellow Sea ecoregion - Hongfei Zhuang; Fangyuan Qu; Zhichuang Lu; Linlin Zhao; Zhaohui Zhang (Reviews in Fish Biology and Fisheries, 2024)

A multiscale dilated attention network for hyperspectral image classification - Chao Tu; Wanjun Liu; Wentao Jiang; Linlin Zhao; Tinghao Yan (Advances in Space Research, 2024)

Comparative analysis of climate-induced habitat shift of economically significant species with diverse ecological preferences in the Northwest Pacific - Wanchuan Dong; Xinlu Bai; Linlin Zhao; Hao Dong; Changdong Liu (Frontiers in Marine Science, 2024)
The Northwest Pacific Ocean is the most productive fishing ground in the Pacific Ocean, with a continuous rise in water temperature since 1990. We developed stacked species distribution models (SSDMs) to estimate the impacts of climate change on the distribution dynamics of economically significant species under three climate change scenarios for the periods 2040-2060 and 2080-2100. Overall, water temperature is the most important factor in shaping the distribution patterns of species, followed by water depth. The predictive results indicate that all the species show a northward migration in the future, and the migration distance varies greatly among species. Most pelagic species will expand their habitats under climate change, implying their stronger adaptability than benthic species. Tropical fishes are more adaptable to climate change than species in other climate zones. Though limitations existed, our study provided baseline information for designing a climate-adaptive, dynamic fishery management strategy for maintaining sustainable fisheries.

Exosomal miR-129-2-3p promotes airway epithelial barrier disruption in PM2.5-aggravated asthma - Caihong Wang; Zeyu Niu; Yan Zhang; Nannan Liu; Xiaotong Ji; Jiayu Tian; Linlin Guan; Dongxing Shi; Huiqiu Zheng; Yuhui Gao; Lifang Zhao; Wenping Zhang; et al. (Journal of Environmental Management, 2024)

Insights of using microbial material in fluoride removal from wastewater: A review - Linlin Cui; Junjun Wang; Hao Zhou; Shiyu Shao; Jue Kang; Xinyi Yu; Hongbo Zhao; Li Shen (Journal of Environmental Management, 2024)

Decreased formulation pH and protein preheating treatment enhance the interaction, storage stability, and bioaccessibility of caseinate-bound lutein/zeaxanthin - Gang Zhang; Linlin He; Xin Qi; Xiao Wang; Yanna Zhao; Qingpeng Wang; Min Liu; Zhuang Ding; Zhengping Wang; Sangeeta Prakash (Food Research International, 2024)

A metal-quercetin-histidine co-coordinated nanoparticle enhances cancer photothermal therapy via reshaping immunosuppressive tumor microenvironment - Shaobo Wang; Shuncheng Yao; Quanhong Hu; Zhuo Wang; Yunchao Zhao; Linlin Li (Chemical Engineering Journal, 2024)

Quantifying the changes in solute transport caused by human influence on river connectivity in inland river basins - Wenhao Zhang; Guofeng Zhu; Ling Zhao; Lei Wang; Dongdong Qiu; Linlin Ye; Siyu Lu; Xinrui Lin (CATENA, 2024)

New Insights into Fish Diversity in the Yellow and Bohai Seas Based on Environmental DNA Technology - Xiaolin Wang; Li Wang; Aiyong Wang; Linlin Zhao (Fishes, 2024)
Marine biodiversity is increasingly threatened by overfishing and marine pollution. A comprehensive understanding of the biodiversity in the Yellow and Bohai Seas is essential for resource conservation. This study conducted a large-scale survey of fishery resources in the Yellow and Bohai Seas to investigate fish community structure and diversity using eDNA technology. The results showed that 57 and 65 fish species were recorded in spring and summer, respectively, with 46 species identified in both seasons. A total of nine dominant species were identified in spring, mainly belonging to Perciformes, while seven dominant species were identified in summer, primarily from Clupeiformes. In different regions, no significant differences in fish α diversity were observed between spring and summer. However, significant seasonal differences were found in both α and β diversity. At the spatial level, fish species in the Yellow and Bohai Seas occupied similar ecological niches. However, at the temporal level, there are certain differences in the ecological niches of fish communities between seasons. Phylogenetic diversity showed no significant differences at the spatial scale, yet notable seasonal variations were observed at the temporal scale, with spring (661.46) significantly exceeding summer (540.30). The Mantel test indicated that nitrate and salinity were key environmental factors influencing α diversity. RDA analysis revealed that the dominant species in spring were mainly influenced by chlorophyll-a and water temperature, while those in summer were mainly affected by water depth, nitrite, water temperature, and salinity.

Ultrasensitive monitoring of PCB77 in environmental samples using a visible-driven photoelectrochemical sensing platform coupling with exonuclease I assisted in target recycling - Lining Su; Guizhen Wang; Linlin Zhao; Yuan Deng; Yujing Guo; Yong Xiao; Huanwen Wang; Chuan Dong; Lifang Fan (Science of The Total Environment, 2024)

Effect of sodium selenite on the synthesis of glucosinolates and antioxidant capacity in Chinese cabbage (Brassica rapa L.ssp.pekinensis) - Yafang Luo; Shuang Zhao; Huan Wang; Huixia Bai; Qi Hu; Linlin Zhao; Tianyi Ma; Zhenyu Fan; Yushu Wang (Physiology and Molecular Biology of Plants, 2024)

Deep-sea mining of massive sulfides: Balancing impacts on biodiversity and ecosystem, technological challenges and law of the sea - Astrid Holzheid; Hongbo Zhao; Tony Cabus; Lei Fan; Thomas Kuhn; Linlin Sun; Chunhui Tao; Matthias Haeckel; Duong Hoang; Norman Kelly; Terue Kihara; Bing Li; et al. (Marine Policy, 2024)

Water-dependent effects of biodegradable microplastics on arsenic fractionation in soil: Insights from enzyme degradation and synchrotron-based X-ray analysis - Kailin Gong; Tianzi Liu; Cheng Peng; Ziyi Zhao; Xiang Xu; Xuechun Shao; Xuan Zhao; Linlin Qiu; Wenwen Xie; Qian Sui; Wei Zhang (Journal of Hazardous Materials, 2024)

Degradation of mycotoxins by pulsed light and evaluation of the safety of degradation products - Lige Qi; Xinyi Zhong; Linlin Gao; Rui Cai; Tianli Yue; Yahong Yuan; Zhouli Wang; Xubo Zhao (Journal of Food Engineering, 2024)

Quantify the extensive crop damage and grain losses caused by underground coal mining subsidence in eastern China - Wenqi Chen; Wu Xiao; Tingting He; Linlin Ruan; Yanling Zhao; Zhenqi Hu (Journal of Cleaner Production, 2024)

Corrigendum to “Shear mechanism of RCS joints with whole column-section diaphragm” Eng Struct 315(2024), 118475 - Weijian Zhao; Yuchen Tao; Siyuan Feng; Linlin Yuan (Engineering Structures, 2024)

Shear mechanism of RCS joints with whole column-section diaphragm - Weijian Zhao; Yuchen Tao; Siyuan Feng; Linlin Yuan (Engineering Structures, 2024)

Boosting TNBC immune checkpoint blockade with an imaging-therapy coupled ozone delivery nano system - Linlin Song; Zhihui Liu; Xiujing He; Tianyue Xu; Meixu Chen; Zihan Xu; Haina Zhao; Jiaojiao Suo; Hong Wang; Zhankun Yang; Shenglan You; Xiaoting Chen; et al. (Chemical Engineering Journal, 2024)

Anti-cancer effects of nitazoxanide in epithelial ovarian cancer in-vitro and in-vivo - Xiangqun Yang; Zhenyan Liu; Xin Wang; Wenda Tian; Taoyu Zhao; Qiaoling Yang; Wenliang Li; Linlin Yang; Hongying Yang; Yue Jia (Chemico-Biological Interactions, 2024)

Dietary Potassium and Magnesium Intake with Risk of Type 2 Diabetes Mellitus Among Rural China: the Henan Rural Cohort Study - Jia Li; Yuqian Li; Chongjian Wang; Zhenxing Mao; Tianyu Yang; Yan Li; Wenguo Xing; Zhuoyang Li; Jiaoyan Zhao; Linlin Li (Biological Trace Element Research, 2024)

From trajectories to network: Delineating the spatial pattern of recreational walking in Guangzhou - Haochen Shi; Linlin Yao; Qiqi Liu; Yankai Wang; Zongcai Wei; Miaoxi Zhao; Ding Ma (Applied Geography, 2024)

From tissue lesions to neurotoxicity: The devastating effects of small-sized nanoplastics on red drum Sciaenops ocellatus - Zhicheng Sun; Xin Peng; Linlin Zhao; Yi Yang; Yugui Zhu; Linlong Wang; Bin Kang (Science of The Total Environment, 2024)

Insight into the mechanisms involved in the improved antagonistic efficacy of Pichia caribbica against postharvest black spot of tomato fruits by combined application with oligochitosan - Xiaoyun Zhang; Yu Xin; Qingrong Yue; Esa Abiso Godana; Linlin Gao; Mengge Dou; Hongyao Zhou; Jun Li; Lina Zhao; Hongyin Zhang (Postharvest Biology and Technology, 2024)

MdWRKY45 contributes to resistance against Botryosphaeria dothidea in apple - Xue Wang; Xiangyue Kong; Linlin Qiu; Wei Kuang; Jun Leng; Yongzhang Wang; Qiang Zhao (Postharvest Biology and Technology, 2024)

Provenance signature and tectono–sedimentary setting of the Permian Shihezi formation (Ordos basin, China): Insights from geochemistry and detrital zircon U–Pb dating - Shuyue Zhu; Lei Liu; Linlin Wang; Zhiwei Wang; Jianling Hu; Jingqi Zhang; Chenggong Zhang; Junxing Zhao; Hongde Chen (Marine and Petroleum Geology, 2024)

Fabrication of stable spherical soybean lipophilic protein nanogel for curcumin delivery: Carbony oxygen and aromatic ring flexibility binding to the beta−barrel - Jianhua Zeng; Junzhe Zou; Lanwei Zhang; Jinlong Zhao; Linlin Liu; Gen Lu; Bingyu Sun; Yanguo Shi; Xiuqing Zhu; Pimin Gong (Food Structure, 2024)

PCDH11X mutation as a potential biomarker for immune checkpoint therapies in lung adenocarcinoma - Manjiao Liu; Meijia Yang; Bei Zhang; Sijian Xia; Jie Zhao; Linlin Yan; Yong Ren; Hao Guo; Jie Zhao (Journal of Molecular Medicine, 2024)

Recent progress in the antidegradation strategies of two-dimensional transition metal carbides (MXenes) - Ying Li; Yudi Li; Linlin Zhao; Siyu Chen; Siren Guo; Xulin Yang; Pan Wang; Kui Li; Fan Lei; Wei Feng; Zihao Mou; Hanjun Wei (Journal of Environmental Chemical Engineering, 2024)

Copper-doped ZIF-67/wood aerogel for effective peroxymonosulfate activation - Linlin Zhao; Wanning Xiong; Ziheng Wang; Jie Ouyang; Mengyao Li; Gonggang Liu; Yongfeng Luo (Journal of Environmental Chemical Engineering, 2024)

A novel metal–organic framework based electrochemical immunosensor for the rapid detection of Salmonella typhimurium detection in milk - Ke Zhan; Linlin Chen; Shanshan Li; Qiuying Yu; Zheng Zhao; Junwei Li; Yunrui Xing; Hongtao Ren; Na Wang; Gaiping Zhang (Food Chemistry, 2024)

A randomised double-blind placebo-controlled trial of a probiotic combination for manipulating the gut microbiota and managing metabolic syndrome - Rui Xiao; Ying Chen; Xiaofeng Zhu; Linlin Wang; Peijun Tian; Xing Jin; Ming Liang; Zehua Chen; Ting Zhang; Long Qian; Qun Wang; Jianxin Zhao; et al. (Food Bioscience, 2024)

Imbalances in the gut microbiota and metabolome are associated with functional constipation in pregnancy - Ruili Pan; Ying Chen; Guopeng Lin; Haojue Wang; Xiaopeng Xu; Linlin Wang; Peijun Tian; Jianxin Zhao; Wei Chen; Gang Wang (Food Bioscience, 2024)

Cellulose-based magnetic nanomaterials immobilized esterases as a reusable and effective detoxification agent for patulin in apple juice - Xiaoshuang Liu; Linlin Gao; Shiqi Li; Leran Wang; Rui Cai; Tianli Yue; Yahong Yuan; Xubo Zhao; Zhouli Wang (Food Control, 2024)

Release characteristics and risk assessment of volatile sulfur compounds in municipal wastewater treatment plants - Linlin Ma; Ruhan Zhao; Jiaxin Li; Qing Yang; Kehua Zou (Environmental Pollution, 2024)

Polycyclic aromatic hydrocarbons exposure and arterial stiffness-related plasma miRNAs: A panel study - Ziqian Zhang; Conghua Bai; Lei Zhao; Linlin Liu; Wenting Guo; Miao Liu; Huihua Yang; Xuefeng Lai; Xiaomin Zhang; Liangle Yang (Environmental Toxicology and Pharmacology, 2024)

Characterization of Nutrients, Heavy Metals, Petroleum and Their Impact on Phytoplankton in Laizhou Bay: Implications for Environmental Management and Monitoring - Kai Wang; Linlin Zhao; Yugui Zhu; Liqiang Yang; Yunfeng Wang; Xuguang Hong (Journal of Ocean University of China, 2024)

Exploring Seasonal Variations in Fish Communities: A Study of the Yellow River Estuary and Its Adjacent Waters Using eDNA and Trawl Surveys - Xiaoyang Wang; Fan Li; Fei Shao; Hongjun Song; Na Song; Xiaomin Zhang; Linlin Zhao (Fishes, 2024)
The Yellow River Estuary and its adjacent waters serve as crucial spawning, foraging, and nursery areas for marine organisms, possessing abundant biological resources. Monitoring fish communities provides a baseline for implementing the sustainable utilization of marine resources. In this study, data were collected from 15 spring surface and bottom sites and 17 summer surface sites using eDNA and trawl surveys. The results showed that 37, 40, and 35 fish species were detected using eDNA in the spring (surface and bottom) and summer (surface), respectively, with 38 fish species caught during summer trawling. The dominant species mainly belonged to Engraulidae of Clupeiformes in the spring and Gobiidae of Perciformes in the summer, characterized by smaller-sized, short-lived, and pelagic fish species. The summer surface communities exhibited higher diversity than the spring surface and bottom communities. NMDS analysis revealed a degree of seasonal differences in fish communities and that there may be a lack of vertical stratification in the spring communities. The pH and DO were identified as the key environmental factors affecting the fish community. Additionally, the combination of eDNA and trawl surveys was regarded as a superior survey method. Our study provides valuable information for understanding seasonal fish communities in the Yellow River Estuary and its adjacent waters, contributing to fishery resource management and conservation in the region.

Towards robust classification of multi-view remote sensing images with partial data availability - Maofan Zhao; Qingyan Meng; Lifeng Wang; Linlin Zhang; Xinli Hu; Wenxu Shi (Remote Sensing of Environment, 2024)

Control of postharvest soft rot of green peppers by Bacillus subtilis through regulating ROS metabolism - Peipei Feng; Xiaoyun Zhang; Esa Abiso Godana; Guillaume Legrand Ngolong Ngea; Solairaj Dhanasekaran; Linlin Gao; Jun Li; Lina Zhao; Hongyin Zhang (Physiological and Molecular Plant Pathology, 2024)

Mitochondrial transcription factor A (TFAM) has 5′-deoxyribose phosphate lyase activity in vitro - Wenxin Zhao; Adil S. Hussen; Bret D. Freudenthal; Zucai Suo; Linlin Zhao (DNA Repair, 2024)

Promoting denitrification via high electron conversion ratio in the iron valence Cycle: Prospects for Pseudomonas sp. JM-7 application in environmental engineering - Bobo Xing; Ji Li; Linlin Li; Nigel J.D. Graham; Binghao Zhao; Xian Li; Wenzheng Yu (Chemical Engineering Journal, 2024)

Bioaerosols in deodorization covers of wastewater treatment plants: Emission characteristics and health risks - Shan Zhao; Yang Liu; Jiang Chang; Jiawei Wang; Hao Peng; Baocong Cui; Jin Bai; Yanjie Wang; Linlin Hua (Chemosphere, 2024)

Evolution behavior of volatile components of shiitake mushrooms during infrared-assisted spouted bed drying - Yiming Xu; Wenchao Liu; Linlin Li; Weiwei Cao; Guangyue Ren; Houdong Shi; Yike Zhao; Junliang Chen; Xu Duan (Food Control, 2024)

Automatic identification of factor profiles can be achieved by improved machine learning model - Bo Xu; Junbo Huang; Yi Ge; Chun Zhang; Han Xu; Feng Wang; Huan Zhao; Linlin Zhang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Environment, 2024)

Medium optimization and dust suppression performance analysis of microbial-based dust suppressant compound by response surface curve method - Xiangming Hu; Zhiyuan Yang; Yanyun Zhao; Yue Dong; Chengcheng Wang; Linlin Zhang; Yiyun Yu; Kai Wu; Liyan Ren (Environmental Science and Pollution Research, 2024)

Influence of polysaccharide-based co-encapsulants on efficiency, stability, and release of vitamins B12 and D3 in multilayered microcapsules - Linlin He; Shihong Hu; Gang Zhang; Xiao Wang; Yanna Zhao; Qingpeng Wang; Min Liu; Zhengping Wang; Prakash Sangeeta; Zhuang Ding (Journal of Food Engineering, 2024)

Release characteristics and risk assessment of volatile sulfur compounds in a municipal wastewater treatment plant with odor collection device - Linlin Ma; Ruhan Zhao; Jiaxin Li; Qing Yang; Yong Liu (Journal of Environmental Management, 2024)

A prospective comparative study on bladder volume measurement with portable ultrasound scanner and CT simulator in pelvic tumor radiotherapy - Fei Bai; Qiuxia Hu; Xiaowei Yao; Ming Cheng; Lina Zhao; Linlin Xu (Physical and Engineering Sciences in Medicine, 2024)
Objective: The consistency of bladder volume is very important in pelvic tumor radiotherapy, and portable bladder scanner is a promising device to measure bladder volume. The purpose of this study was to investigate whether the bladder volume of patients with pelvic tumor treated with radiotherapy can be accurately measured using the Meike Palm Bladder Scanner PBSV3.2 manufactured in China and the accuracy of its measurement under different influencing factors. Methods: A total of 165 patients with pelvic tumor undergoing radiotherapy were prospectively collected. The bladder volume was measured with PBSV3.2 before simulated localization. CT simulated localization was performed when the bladder volume was 200-400ml. The bladder volume was measured with PBSV3.2 immediately after localization and recorded. The bladder volume was then delineated on CT simulation images and recorded. To compare the consistency of CT simulation bladder volume and bladder volume measured by PBSV3.2. To investigate the accuracy of PBSV3.2 in different sex, age, treatment purpose, and bladder volume. Results: There was a significant positive correlation with bladder volume on CT and PBSV3.2 ( r = 0.874; p < 0.001). The mean difference between CT measured values and PBSV3.2 was (-0.14 ± 50.17) ml. The results of the different variables showed that the overall mean of PBSV3.2 and CT measurements were statistically different in the age ≥ 65 years, bladder volumes > 400ml and ≤ 400ml groups ( p = 0.028, 0.002, 0.001). There was no statistical significance between the remaining variables. The volume difference between PBSV3.2 measurement and CT was 12.87ml in male patients, which was larger than that in female patients 3.27ml. Pearson correlation analysis showed that the correlation coefficient was 0.473 for bladder volume greater than 400ml and 0.868 for bladder volume less than 400ml; the correlation coefficient of the other variables ranged from 0.802 to 0.893. Conclusion: This is the first large-sample study to evaluate the accuracy of PBSV3.2 in a pelvic tumor radiotherapy population using the convenient bladder scanner PBSV3.2 made in China. PBSV3.2 provides an acceptable indicator for monitoring bladder volume in patients with pelvic radiotherapy. It is recommended to monitor bladder volume with PBSV3.2 when the planned bladder volume is 200-400ml. For male and patients ≥ 65 years old, at least two repeat measurements are required when using a bladder scanner and the volume should be corrected by using a modified feature to improve bladder volume consistency.

Adsorption of high-temperature CO2 by Ca2+/Na+-doped lithium orthosilicate: characterization, kinetics, and recycle - Dongling Zhao; Linlin Geng; Yanfei Jia; Jianwen Wei; Xiaobin Zhou; Lei Liao (Environmental Science and Pollution Research, 2024)

The mediation effect of asprosin on the association between ambient air pollution and diabetes mellitus in the elderly population in Taiyuan, China - Lulu Song; Yuhui Gao; Jiayu Tian; Nannan Liu; Halimaimaiti Nasier; Caihong Wang; Huiqiu Zhen; Linlin Guan; Zeyu Niu; Dongxing Shi; Hongmei Zhang; Lifang Zhao; et al. (Environmental Science and Pollution Research, 2024)

Colorimetric microneedle sensor using deep learning algorithm for meat freshness monitoring - Jie Wang; Linlin Xia; Han Liu; Chong Zhao; Siyu Ming; Jingyi Wu (Chemical Engineering Journal, 2024)

Green technology innovation and regional carbon emissions: analysis based on heterogeneous treatment effect modeling - Maosen Xia; Linlin Dong; Xin Zhao; Lingling Jiang (Environmental Science and Pollution Research, 2024)

GhFB15 is an F-box protein that modulates the response to salinity by regulating flavonoid biosynthesis - Zhao Geng; Haikuan Dou; Jianguang Liu; Guiyuan Zhao; Zetong An; Linlin Liu; Ning Zhao; Hanshuang Zhang; Yongqiang Wang (Plant Science, 2024)

Controllable synthesis of polyaspartic acid: Studying into the chain length effect for calcium scale inhibition - Meng-Long Zhang; Zheng Ruan; Yu Han; Zhi-Wei Cao; Linlin Zhao; Yuan-Qing Xu; Zhong-Yan Cao; Wen-Yan Shi; Ying Xu (Desalination, 2024)

Applying an ensemble of small models in predicting habitat suitability of invasive M. sallei along the southern coast of China - Hao Dong; Jie Liu; Linlin Zhao; Changdong Liu (Marine Pollution Bulletin, 2023)

Effect mechanisms of leading-edge tubercle on blade cavitation control in a waterjet pump - Guoshou Zhao; Ning Liang; Qianqian Li; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2023)

Plant-based meat analogues enhance the gastrointestinal motility function and appetite of mice by specific volatile compounds and peptides - Yunting Xie; Linlin Cai; Mengzhen Ding; Kai Shan; Di Zhao; Guanghong Zhou; Chunbao Li (Food Research International, 2023)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

PM2.5-bound metals and blood metals are associated with pulmonary function and Th17/Treg imbalance: A panel study of asthmatic adults - Nannan Liu; Dan Wang; Jiayu Tian; Xin Wang; Hao Shi; Caihong Wang; Yi Jiang; Min Pang; Xiaozhou Fan; Jing Zhao; Liangpo Liu; Hongyan Wu; et al. (Chemosphere, 2023)

Strategies for the coordinated control of particulate matter and carbon dioxide under multiple combined pollution conditions - Zhenyu Wang; Huan Zhao; Han Xu; Jie Li; Tong Ma; Linlin Zhang; Yinchang Feng; Guoliang Shi (Science of The Total Environment, 2023)

Biomineralization of uranium by Desulfovibrio desulfuricans A3-21ZLL under various hydrochemical conditions - Bei Zhao; Xin Chen; Hongliang Chen; Linlin Zhang; Jiang Li; Yadan Guo; Haiyan Liu; Zhongkui Zhou; Pingchao Ke; Zhanxue Sun (Environmental Research, 2023)

A quantitative analysis of the impact of reclamation on the stability of coastal wetlands - Yanhui Chen; Linlin Cui; Guosheng Li; Jiping Liu; Lijuan Li; Dandan Zhao (Ocean & Coastal Management, 2023)

A novel ZnFe2O4 intermediate layer for improving the electrocatalytic performance of Ti/Ce-PbO2 anode toward Levofloxacin removal - Linlin Dong; Zhong Zhuang; Guohua Dong; Hao Zhang; Min Zhu; Zhuanfang Zhang; Ming Zhao; Jinlong Li; Wenzhi Zhang (Journal of Environmental Chemical Engineering, 2023)

Reaction pathways control of long-chain alkanes hydroisomerization and hydrocracking via tailoring the metal-acid sites intimacy - Wenli Zhao; Linlin Liu; Xiaopo Niu; Xinyue Yang; Jiuyi Sun; Qingfa Wang (Fuel, 2023)

Expression analysis, clinical significance and potential function of PLXNB2 in acute myeloid leukaemia - Zhibo Guo; Dan Guo; Desheng Kong; Sicheng Bian; Linlin Zhao; Qi Li; Leilei Lin; Jiali Hao; Lili Sun; Yinghua Li (Molecular Biology Reports, 2023)

Genomic Characteristics of Okamejei kenojei and the Implications to Its Evolutionary Biology Study - Na Song; Siyu Ma; Xiang Zhao; Jiabao Zhao; Linlin Zhao (Marine Biotechnology, 2023)

Application of interim PET-CT in first-line treatment decision-making for lymphoma - Linlin Huang; Yi Zhao; Jingsong He (Journal of Zhejiang University-SCIENCE B, 2023)

Application of carbon dots in food preservation: a critical review for packaging enhancers and food preservatives - Linlin Zhao; Min Zhang; Arun S. Mujumdar; Haixiang Wang (Critical Reviews in Food Science and Nutrition, 2023)

Effect of non-permeable cryoprotectant sucrose on the development of spotted knifejaw (Oplegnathus punctatus) embryos - Linlin Li; Yongsheng Tian; Zhentong Li; Pengfei Duan; Xinyi Wang; Shuai Chen; Linna Wang; Yang Liu; Qingbin Wang; Wensheng Li; Xia Zhao; Wenhui Ma; et al. (Cryobiology, 2023)

Nitrogen addition impacts on soil phosphorus transformations depending upon its influences on soil organic carbon and microbial biomass in temperate larch forests across northern China - Linlin Zheng; Qiong Zhao; Guigang Lin; Xin Hong; Dehui Zeng (CATENA, 2023)

Schemes for enhanced antioxidant stability in frying meat: a review of frying process using single oil and blended oils - Ju Shen; Min Zhang; Linlin Zhao; Arun S. Mujumdar; Haixiang Wang (Critical Reviews in Food Science and Nutrition, 2023)

Insights into gas flow behavior in venturi aerator by CFD-PBM model and verification of its efficiency in sludge reduction through O3 aeration - Hongli Li; Qilei Zhang; Ming Zeng; Jingguo Cao; Qingyu Zhao; Linlin Hao (Journal of Water Process Engineering, 2023)

Urinary phthalate metabolites and heart rate variability: A panel study - Ziqian Zhang; Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Jie Yu; Huihua Yang; Xuefeng Lai; Xiaomin Zhang; Liangle Yang (Environmental Pollution, 2023)

Strong and continuous MXene/sodium alginate composite fibers prepared by immersion rotary jet spinning process with outstanding electromagnetic interference shielding performance - Guoxin Zhao; Chao Sui; Linlin Miao; Junjiao Li; Lei Wen; Gong Cheng; Chenxi Zhao; Weizhe Hao; Yuna Sang; Jiaxuan Li; Zhuochao Zhang; Yushun Zhao; et al. (Chemical Engineering Journal, 2023)

High-pressure synthesis of fully sp2-hybridized polymeric nitrogen layer in potassium supernitride - Minghong Sui; Shuang Liu; Peng Wang; Nianlong Zou; Qing Dong; Miao Zhou; Shifeng Niu; Lei Yue; Zitong Zhao; Linlin Guo; Bo Liu; Ran Liu; et al. (Science Bulletin, 2023)

Manipulating electron redistribution induced by asymmetric coordination for electrocatalytic water oxidation at a high current density - Sheng Zhao; Feng Hu; Lijie Yin; Linlin Li; Shengjie Peng (Science Bulletin, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Self-powered energy harvesting and implantable storage system based on hydrogel-enabled all-solid-state supercapacitor and triboelectric nanogenerator - Zhuo Wang; Shuncheng Yao; Shaobo Wang; Zhirong Liu; Xingyi Wan; Quanhong Hu; Yunchao Zhao; Cheng Xiong; Linlin Li (Chemical Engineering Journal, 2023)

Allosteric synthetic antibody (Allo-SyAb) for improved cancer immunotherapy - Jiajing Chen; Mengchen Xu; Yongxin Zhang; Linlin Xu; Shuyue Zhao; Yingli An; Rujiang Ma; Yang Liu; Feihe Ma; Linqi Shi (Chemical Engineering Journal, 2023)

Accumulation and speciation of arsenic in Eisenia fetida in sodium arsenite spiked soils - A dynamic interaction between soil and earthworms - Weiqin Xing; Hongpei Geng; Yali Wang; Linlin Zhao; Yongqiang Yang; Yale Wang; Shuhang Tian; Yongxin Cao; Zhe Zhang; Liping Li (Chemosphere, 2023)

Water/acid/reductive biomass leaching of Cr(VI) in chromium ore processing residue (CORP) for safe discharge of effluent and to recover Cr(III) and gypsum - Zhenan Jin; Baoren Wang; Feixian Zheng; Linlin Tong; Jiafeng Li; Qianfei Zhao; Liuhan Jin (Hydrometallurgy, 2023)

Mineralogical characteristics and recovery process optimization analysis of a refractory gold ore with gold particles mainly encapsulated in pyrite and Arsenopyrite - Jiafeng Li; Hongying Yang; Rongxin Zhao; Linlin Tong; Qiao Chen (Geochemistry, 2023)

Comparison and quantification of estrogen receptor-mediated responsiveness to endocrine disruptors in bivalves by using complementary model and a novel yeast assay approach - Liru Liu; Jingjing Miao; Peipei Liu; Anran Zhao; Linlin Yao; Luqing Pan (Environmental Pollution, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

Phthalate Mixture Exposure is Associated with Elevated Blood Pressure in Chinese Children: A Panel Study - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Meng Li; Shuang Chen; Jie Yu; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Exposure and Health, 2023)

Contribution of the TGFβ signaling pathway to pigmentation in sea cucumber (Apostichopus japonicus) - Linlin Yao; Bin Zhao; Qi Wang; Xuyang Jiang; Sha Han; Wei Hu; Chenglin Li (Frontiers in Marine Science, 2023)
Pigmentation mediated by the transforming growth factor β (TGFβ) signaling pathway is a key trait for understanding environmental adaptability and species stability. In this study, TGFβ signaling pathway members and their expression patterns in different color morphs of the sea cucumber Apostichopus japonicus were evaluated. Using a bioinformatics approach, 22 protein sequences of TGFβ signaling pathway members in A. japonicus were classified, including 14 that were identified for the first time in the species, including 7 ligands, 6 receptors, and 1 R-Smad. We further evaluated mRNA expression data for different color morphs and pigmentation periods. These results support the hypothesis that both subfamilies of the TGFβ superfamily, i.e., the TGFβ/activin/Nodal and BMP/GDF/AMH subfamilies, are involved in the regulation of pigmentation in A. japonicus . The former subfamily was complete and contributes to the different color morphs. The BMP/GDF/AMH subfamily was incomplete. BMP2/4-induced differentiation of white adipocytes was regulated by the BMP2/4–ACVR2A–Smad1 signaling pathway. These findings provide insight into the TGFβ family in early chordate evolution as well as the molecular basis of color variation in an economically valuable species.

Comprehensively investigating performance and potential mechanism of anammox-based nitrogen removal process with different microbial morphologies under mainstream conditions - Shuang Liu; Xinxin Xu; Hongli Li; Ming Zeng; Linlin Hao; Ruihua Zhao; Jingguo Cao; Nan Wu; Zongpeng Zhang (Journal of Environmental Chemical Engineering, 2023)

Air pollution exposure and ovarian reserve impairment in Shandong province, China: The effects of particulate matter size and exposure window - Lihong Pang; Wenhao Yu; Jiale Lv; Yunde Dou; Han Zhao; Shanshan Li; Yuming Guo; Gongbo Chen; Linlin Cui; Jingmei Hu; Yueran Zhao; Qi Zhao; et al. (Environmental Research, 2023)

Regulation of MIL-88B(Fe) to design FeS2 core-shelled hollow sphere as high-rate anode for a full sodium-ion battery - Linlin Ma; Baoxiu Hou; Hui Zhang; Shitao Yuan; Bin Zhao; Yuan Liu; Xinran Qi; Haiyan Liu; Shuaihua Zhang; Jianjun Song; Xiaoxian Zhao (Chemical Engineering Journal, 2023)

Short telomeres impede germ cell specification by upregulating MAPK and TGFβ signaling - Chenglei Tian; Dai Heng; Nannan Zhao; Linlin Liu; Xiaoyan Sheng; Jiyu Chen; Lin Liu (Science China Life Sciences, 2023)

Acrylamide Induces Neurotoxicity in SH-SY5Y Cells via NLRP3-mediated Pyroptosis - Mengyao Zhao; Boya Zhang; Linlin Deng; Liming Zhao (Molecular Neurobiology, 2023)

Geochronology and geochemistry of the Late Triassic intrusive rocks in the Liaodong Peninsula, NE China: Petrogenesis and implications for early Mesozoic tectonic evolution - Peng Zhang; Yan Zhao; Linlin Kou; Deming Sha (International Geology Review, 2023)

Heterosis in growth and low temperature tolerance in Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) - Shuai Chen; Yongsheng Tian; Zhentong Li; Yang Liu; Ziqi Li; Pengfei Duan; Linlin Li; Xinyi Wang; Linna Wang; Xinlei He; Xia Zhao; Wensheng Li; et al. (Aquaculture, 2023)

Genesis of the Xinfang gold deposit, Liaodong Peninsula: Constraints from fluid inclusions, H-O-S-Pb isotopes, pyrite trace element concentrations, and chronology - Peng Zhang; Yan Zhao; Linlin Kou; Hong zhi Yang (Gondwana Research, 2023)

Estimating small structural motions from multi-view video measurement - Enjian Cai; Yi Zhang; Xiaodong Ji; Xinzheng Lu; Linlin Xie; Yuncheng Zhuang; Taisen Zhao; Guangwei Lin (Engineering Structures, 2023)

Flexible and highly piezoelectric nanofibers with organic–inorganic coaxial structure for self-powered physiological multimodal sensing - Xingyi Wan; Zhuo Wang; Xinyang Zhao; Quanhong Hu; Zhou Li; Zhong Lin Wang; Linlin Li (Chemical Engineering Journal, 2023)

TRIM11, a new target of p53, facilitates the migration and invasion of nasopharyngeal carcinoma cells - Ziyi Zhao; Jinkuang Deng; Ming Lu; Jun Yang; Linlin Chen; DianYuan Li; Yi Sang (Molecular Biology Reports, 2023)
Background Although tripartite motif-containing protein 11 (TRIM11) is known to be associated with a variety of cancers, its role in nasopharyngeal carcinoma (NPC) is unclear. Methods and results To investigate the role of TRIM11 in NPC, TRIM11 was stably overexpressed in 6–10B and CNE2 cells with lentiviral vectors and knocked down in S18 and 5–8F cells using the CRISPR/Cas9 system. Transwell assays and wound-healing assays revealed that TRIM11 facilitated the migration and invasion of NPC cells. Mechanistically, we found that p53 inhibits TRIM11 expression by binding to its promoter. Conclusions TRIM11 may serve as a potential diagnostic marker for NPC and has a certain therapeutic value.

Fluoride-Induced Sperm Damage and HuR-Mediated Excessive Apoptosis and Autophagy in Spermatocytes - Yanyan Li; Jianbin Zhang; Linlin Sun; Hongyu Zhao; Xiaohan Jia; Yingri Zhang; Yuanbin Li (Biological Trace Element Research, 2023)

High-quality chromosome-level genome assembly of Pacific cod, Gadus macrocephalus - Yiqing Ma; Yuan Li; Chen Jiang; Li Zheng; Shenghao Liu; Linlin Zhao (Frontiers in Marine Science, 2022)

Three periods of gold mineralization in the Liaodong Peninsula, North China Craton - Peng Zhang; Linlin Kou; Yang Zhao (International Geology Review, 2022)

High levels of serum IL-10 indicate disease progression, extramedullary involvement, and poor prognosis in multiple myeloma - Xiaoyan Yue; Linlin Huang; Yang Yang; Yi Zhao; Donghua He; Xiaoyan Han; Gaofeng Zheng; Yi Li; Enfan Zhang; Zhen Cai; Xin Huang; Jingsong He (Journal of Zhejiang University-SCIENCE B, 2022)

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

Identification and Characterization of the Homeobox Gene Family in Fusarium pseudograminearum Reveal Their Roles in Pathogenicity - Yuming Ma; Jingya Zhao; Wenbo Chen; Xuejing Geng; Tianli He; Shengli Ding; Bingjian Sun; Honglian Li; Linlin Chen (Biochemical Genetics, 2022)

The Structure and Function of Microbial Community in Rhizospheric Soil of American Ginseng (Panax quinquefolius L.) Changed with Planting Years - Guozhong Chen; Ying Xue; Xin Yu; Chongwei Li; Yuping Hou; Hongwei Zhu; Linlin Jiang; Weibo Zheng; Zhibin Feng; Youzhi Li; Wenli Tang; Xiaoyu Zhao; et al. (Current Microbiology, 2022)

Coffin-Siris syndrome in two chinese patients with novel pathogenic variants of ARID1A and SMARCA4 - Mingjie Liu; Linlin Wan; Chunrong Wang; Hongyu Yuan; Yun Peng; Na Wan; Zhichao Tang; Xinrong Yuan; Daji Chen; Zhe Long; Yuting Shi; Rong Qiu; et al. (Genes & Genomics, 2022)

AlgaeMask: An Instance Segmentation Network for Floating Algae Detection - Xiaoliang Wang; Lei Wang; Liangyu Chen; Feng Zhang; Kuo Chen; Zhiwei Zhang; Yibo Zou; Linlin Zhao (Journal of Marine Science and Engineering, 2022)
Video surveillance on the offshore booster station and around the coast is a effective way to monitor floating macroalgae. Previous studies on floating algae detection are mainly based on traditional image segmentation methods. However, these algorithms cannot effectively solve the problem of extracting Ulva prolifra and Sargassum at different sizes and views. Recently, instance segmentation methods have achieved great success in computer vision applications. In this paper, based on the CenterMask network, a novel instance segmentation architecture named AlgaeMask is proposed for floating algae detection from the surveillance videos. To address the feature extraction ability of the network in the inter-dependencies for position and channel, we introduce a new OSA-V3 module with the dual-attention block, which consists of a position attention mechanism and channel attention mechanism. Meanwhile, scale-equalizing pyramid convolution is introduced to solve the problem of scale difference. Finally, we introduce the feature decoder module based on FCOS head and segmentation head to obtain the segmentation area of floating algae in each bounding box. The extensive experiment results show that the average precision of our AlgaeMask in the tasks of mask segmentation and box detection can reach 44.22% and 48.13%, respectively, which has 15.09% and 8.24% improvement over CenterMask. In addition, the AlgaeMask can meet the real-time requirements of floating algae detection.

Estimating the impacts of climate change on the habitat suitability of common minke whales integrating local adaptation - Bin Sun; Linlin Zhao; Fei Shao; Zhichuang Lu; Jiashen Tian; Changdong Liu (Frontiers in Marine Science, 2022)
Climate change is exerting unprecedented effects on the habitats of marine mammals. Common minke whales ( Balaenoptera acutorostrata ) have suffered immense harm from commercial whaling, and the recovery of this species is likely threatened by climate change. To better manage and conserve this species, it is important to predict its current habitat distribution and the potential change under future climate change scenarios. Such predictions are typically generated by species distribution models (SDMs), which construct a correlation between species occurrence data and its habitat environmental variables. SDMs are commonly constructed at the species level, assuming a homogenous response of the species to climatic variables across their entire geographic range. Spatially segregated populations from the same species inhabit distinct environments and gradually adapt to the local conditions, resulting in niche differentiation among populations. Species-level SDMs that ignore the effects of local adaptation mask differences in population responses to climate change and might present an unrealistic picture of potential species distributions. Based on morphological and genetic evidence, the common minke whale was divided into three populations: the North Atlantic population (NAP), Southern Hemisphere population (SHP) and North Pacific population (NPP); these populations inhabit isolated geographic areas with distinct environmental conditions. We quantified the realized niches of these populations and found evidence of significant ecological niche differentiation. We then constructed SDMs at the species and population levels and compared the predictions from these two types of models under different climate change scenarios. Both types of models projected similar change trends in species range, with a contraction of future suitable habitats for the NAP and SHP and an expansion for the NPP. However, the magnitudes of this change differed; the population-level model projected more optimistic results for the SHP and NAP, indicating less habitat loss. This study highlighted the importance of considering local adaptation when estimating the impact of climate change on species habitat suitability. These spatiotemporal predictions provide essential knowledge for designing climate-adaptive conservation and management strategies, such as the delimitation of mobile marine protected areas (MPAs).

High Genetic Connectivity Inferred from Whole-Genome Resequencing Provides Insight into the Phylogeographic Pattern of Larimichthys polyactis - Jian Zheng; Linlin Zhao; Xiang Zhao; Tianxiang Gao; Na Song (Marine Biotechnology, 2022)

The Paleogene to Neogene climate evolution and driving factors on the Qinghai-Tibetan Plateau - Jiagang Zhao; Shufeng Li; Alexander Farnsworth; Paul J. Valdes; Tammo Reichgelt; Linlin Chen; Zhekun Zhou; Tao Su (Science China Earth Sciences, 2022)

Deep-Sea-Derived Fungi as Valuable Producers of Cytotoxic Secondary Metabolites and Their Leads Potential - Guangrong Zhao; Wenli Tang; Jianlong Zhang; Peimin Shi; Youzhi Li; Jiao Wang; Qingqin Shen; Haixia Si; Linlin Jiang; Xin Yu; Hongwei Zhu; Guozhong Chen; et al. (Frontiers in Marine Science, 2022)
Cancer is the leading lethal disease worldwide. Natural products have contributed significantly to the development of approved therapeutic agents. Therefore, research into new bioactive naturally sourced metabolites with lead potential is urgently needed. It is well-known that marine microorganisms are by far one of the most notable and prolific sources of bioactive natural products. Among them, deep-sea-derived fungi are extraordinarily adapted and metabolically active under extreme environmental conditions, which enable them to produce a large number of novel secondary metabolites. Chemical examination of deep-sea-derived fungi has yielded enormous amounts of cytotoxic natural products and potential drug leads. This review summarizes a total of 229 cytotoxic compounds isolated from deep-sea-derived fungi from 2010 to 2021. The emphasis is on the unique chemical diversity of these metabolic products, together with their relevant cytotoxic properties. Among the isolated metabolites, 82 compounds have been found to possess moderate to potent cytotoxic activities. Meanwhile, we also highlight some compounds with potent cytotoxicities (namely “star molecules”) considering their high drug lead potential. This review reveals deep-sea-derived fungi as considerable resources for the development of new drugs and the potential of the newly discovered secondary metabolites as valuable antitumor lead compounds.

Chromosomal Assembly of the Hexagrammos agrammus Genome via Third-Generation DNA Sequencing and Hi-C Technology - Linlin Zhao; Shenghao Liu; Shouqiang Wang; Tianyan Yang; Qi Liu; Tianxiang Gao (Frontiers in Marine Science, 2022)

The involvement of oxidative stress, neuronal lesions, neurotransmission impairment, and neuroinflammation in acrylamide-induced neurotoxicity in C57/BL6 mice - Mengyao Zhao; Linlin Deng; Xiaoxuan Lu; Liqiang Fan; Yang Zhu; Liming Zhao (Environmental Science and Pollution Research, 2022)

Genomic analysis of a recombinant coxsackievirus A19 identified in Xinxiang, China, in 2019 - Liang Yi; Li Zhang; Linlin Feng; Xubo Luan; Qian Zhao; Pengwei Xu; Yinbiao Wang; Ling Tao; Weidong Wu (Archives of Virology, 2022)

p53 m6A modulation sensitizes hepatocellular carcinoma to apatinib through apoptosis - Weiwei Ke; Linlin Zhang; Xiangxuan Zhao; Zaiming Lu (Apoptosis, 2022)

Chromosome-Level Genome Assembly of Acanthogobius ommaturus Provides Insights Into Evolution and Lipid Metabolism - Yu Pan; Zhicheng Sun; Tianxiang Gao; Linlin Zhao; Na Song (Frontiers in Marine Science, 2022)
Acanthogobius ommaturus is a large, fast-growing annual fish widely distributed in coastal and estuarine areas. The adults will die after breeding, and its life cycle is only 1 year. The first chromosome-level genome assembly of A. ommaturus was obtained by PacBio and Hi-C sequencing in this study. The final genome assembly after Hi-C correction was 921.49 Mb, with contig N50 and scaffold N50 values of 15.70 Mb and 40.99 Mb, respectively. The assembled sequences were anchored to 22 chromosomes by using Hi-C data. A total of 18,752 protein-coding genes were predicted, 97.90% of which were successfully annotated. Benchmarking Universal Single-Copy Orthologs (BUSCO) assessment results for genome and gene annotations were 93.6% and 84.6%, respectively. A. ommaturus is phylogenetically closely related to Periophthalmodon magnuspinnatus and Boleophthalmus pectinirostris , diverging approximately 31.9 MYA with the two goby species. The A. ommaturus genome displayed 597 expanded and 3,094 contracted gene families compared with the common ancestor. A total of 1,155 positive selected genes (PSGs) ( p < 0.05) were identified. Based on comparative genomic analyses, we obtained several expanded genes such as acsbg2 , lrp1 , lrp6 , and znf638 involved in lipid metabolism. A total of twenty candidate genes were identified under positive selection, which associated with lifespan including ercc6 , igf1 , polg , and tert . Interspecific collinearity analysis showed a high genomic synteny between A. ommaturus and P. magnuspinnatus . The effective population size of A. ommaturus decreased drastically during 200–100 Ka because of Guxiang ice age and then increased gradually following warm periods. This study provides pivotal genetic resources for in-depth biological and evolutionary studies, and underlies the molecular basis for lipid metabolism.

Effectiveness of Selenium on Chondrocyte Glycoprotein Glycosylation Which Play Important Roles in the Pathogenesis of an Endemic Osteoarthritis, Kashin–Beck Disease - Sen Wang; Lingling Geng; Guanghui Zhao; Peilin Meng; Linlin Yuan; Xiong Guo (Biological Trace Element Research, 2022)

Lower activity time constraint on the ore-controlling Erdaogou fault in the Qingchengzi orefield of the Liaodong Peninsula, NE China - Yan Zhao; Yuewen Feng; Peng Zhang; Linlin Kou; Zhongzhu Yang; Shenghui Li; Wei Wang (Acta Geochimica, 2022)

Traditional fermented soybean products: processing, flavor formation, nutritional and biological activities - Libo Liu; Xiaoqian Chen; Linlin Hao; Guofang Zhang; Zhao Jin; Chun Li; Yuzhuo Yang; Jiajia Rao; Bingcan Chen (Critical Reviews in Food Science and Nutrition, 2022)

Katabatic Flow Structures Indicative of the Flux Dissimilarity for Stable Stratification - Xiaofeng Guo; Wei Yang; Zhiqiu Gao; Linlin Wang; Jinkyu Hong; Baohong Ding; Long Zhao; Degang Zhou; Kun Yang (Boundary-Layer Meteorology, 2022)

Full-Length Transcriptome of the Whale Shark (Rhincodon typus) Facilitates the Genome Information - Fangrui Lou; Li Wang; Zhiyang Wang; Lei Wang; Linlin Zhao; Qingjie Zhou; Zhichuang Lu; Yongzheng Tang (Frontiers in Marine Science, 2022)
Rhincodon typus is a keystone and indicator species in marine ecosystems. Meanwhile, R. typus has been listed on the IUCN red list of vulnerable species. Here we used ONT platform to determine the full-length (FL) transcriptome of R. typus and obtained 14,930 FL transcripts. Among all FL transcripts, 14,915 transcripts were covered 11,892 genetic loci and 1,642 novel genetic loci were further found. Meanwhile, we identified 714 novel transcripts by compared FL transcripts with the R. typus genome. Based on FL transcripts, we also predicted the distribution patterns of ASs, LncRNAs, polyAs, CDSs and methylation sites on FL transcriptome of R. typus . Furthermore, a total of 31,021 (97.86%) CDSs can obtained annotation information. Overall, our work firstly provided the FL transcriptome and these sequences complete the annotated R. typus genome information. Furthermore, these information are a potential resource to study biological processes of R. typus .

Genetic background and cis-organization regulate ALDH7B4 gene expression in Eutrema salsugineum: a promoter analysis case study - Quancan Hou; Tianye Zhang; Wei Zhao; Linlin Wang; Lu Lu; Yuchen Qi; Dorothea Bartels (Planta, 2022)

Intensification of Downslope Nutrient Transport and Associated Biological Responses Over the Northeastern South China Sea During Wind-Driven Downwelling: A Modeling Study - Aiqin Han; Jianping Gan; Minhan Dai; Zhongming Lu; Linlin Liang; Xiaozheng Zhao (Frontiers in Marine Science, 2021)
Coastal downwelling is generally considered to have a limited biological effect compared with coastal upwelling. In this study, downslope transport of nearshore, nutrient-enriched waters during downwelling is found to induce distinct biological productivity in the water column over the northeastern South China Sea (NSCS). By conducting a process-driven study over a widened shelf with intensified downwelling in the NSCS, we investigated the biophysical processes associated with strong nutrient enrichment in the water column of downwelled waters. These processes and underlying mechanisms are largely unreported and remain unclear. Field measurements and a three-dimensional coupled physical-biological model incorporating nitrate ( N ), phytoplankton ( P ), zooplankton ( Z ), and detritus ( D ) were utilized to investigate distinct cross-shore nutrient transport over the uniquely widened NSCS shelf. We revealed that intensified downwelling circulation, dynamically induced by the widened shelf topography, enhanced chlorophyll a and biological productivity in a strip of well-mixed water over the inner shelf as well as in the downwelled water over the mid-shelf. Strong time lags and spatial differences existed among N , P , and Z because of the physical transport and the ensuing biogeochemical response. The intensified downslope transport of nutrient-rich coastal water formed distinct cross-shore wedge-shaped P , Z , and D structures, while N was rapidly consumed in the water column. This study illustrates the underlying coupled physical-biogeochemical processes associated with the observed biogeochemical response to wind-driven downwelling circulation over the variable shelf, which are commonly found in coastal oceans worldwide.

Isocitrate dehydrogenase of Bacillus cereus is involved in biofilm formation - Linlin Zhao; Qing Liu; Qiubin Huang; Fengying Liu; Huiping Liu; Gang Wang (World Journal of Microbiology and Biotechnology, 2021)

Recent advances in functional 3D printing of foods: a review of functions of ingredients and internal structures - Linlin Zhao; Min Zhang; Bimal Chitrakar; Benu Adhikari (Critical Reviews in Food Science and Nutrition, 2021)

Functional Trait Responses of Macrobenthos to Anthropogenic Pressure in Three Temperate Intertidal Communities - Jian-Yu Dong; Linlin Zhao; Xiaolong Yang; Xin Sun; Xiumei Zhang (Frontiers in Marine Science, 2021)
With the increasing impact of human activities on marine ecosystems, there is a growing need to assess how the components of marine ecosystems (e.g., macrobenthos) respond to these anthropogenic pressures. In this work, the trait-based approach was used to assess the effects of anthropogenic pressures represented by the area of land-based aquaculture pond (Pond Area) and heavy metals on the macrobenthic communities in three intertidal zones[Aoshan Bay (AO), Wenquan River and Daren River (RW), and Xiaodao Bay (XD)] of Laoshan Bay, Shandong Peninsula, China. Compared with RW and XD, AO was under more pressure in terms of the average concentrations of heavy metals and total organic carbon (TOC) in sediments and also in the Pond Area. Fuzzy correspondence analysis (FCA) showed that there were significant differences in the composition of functional traits among the three regions (PERMANOVA; p < 0.05). In the highly polluted area, macrobenthic communities exhibited a combination of traits, such as relatively short life span, weak mobility, feeding on deposits, and more tolerant to organic matter, whereas in a less polluted area, they exhibited a combination of traits, such as relatively long life span, relatively high mobility, and more sensitivity to organic matter. The RDA results showed that the distribution of the trait modalities was significantly affected by heavy metals (Hg and Cd), TOC, Pond Area, and sampled location. Variation partitioning analysis (VPA) indicated that the shared influence of sediment-related pollution factors and Pond Area contributed most to the variance of the functional traits, which implied that human activities directly and/or indirectly lead to changes in functional traits of macrobenthic communities in the intertidal zones.

Climate change impacts on China’s marine ecosystems - Bin Kang; Gretta T. Pecl; Longshan Lin; Peng Sun; Peidong Zhang; Yuan Li; Linlin Zhao; Xin Peng; Yunrong Yan; Chunyan Shen; Wentao Niu (Reviews in Fish Biology and Fisheries, 2021)

Phylogenomics Based on Transcriptome Data Provides Evidence for the Internal Phylogenetic Relationships and Potential Terrestrial Evolutionary Genes of Lungfish - Linlin Zhao; Shouqiang Wang; Fangrui Lou; Tianxiang Gao; Zhiqiang Han (Frontiers in Marine Science, 2021)
The evolutionary relationships of lungfish can provide crucial information on the transition from Sarcopterygii to tetrapods. Phylogenomics is necessary to explore accurate internal phylogenetic relationships among all lungfish species. In the context of the lack of genome-wide genetic information for Protopterus amphibious , we are the first to systematically report the transcriptome of P. amphibius and these sequences can be used to enrich the genome-wide genetic information of lungfish. Meanwhile, we also found significant differences in the expression levels of 3,189 genes between the lung and heart of P. amphibious . Based on phylogenomics, 1,094 shared orthologous genes were identified and then applied to reconstruct the internal phylogenetic structure of lungfish species. The reconstructed phylogenetic relationships provide evidence that lungfish is the sister group of terrestrial vertebrates and that Neoceratodus forsteri is the most primitive lungfish. Moreover, the divergence time between the most primitive lungfish and other lungfish species is between 186.11 and 195.36 MYA. Finally, 43 protein metabolism-related, stress response-related, and skeletogenesis-related genes were found to have undergone positive selection and fast evolution in N. forsteri . We suspected that these genes possibly helped ancient fish adapt to the new terrestrial environment and ultimately contributed to its spreading to land.

Genome-wide association study of grain shapes in Aegilops tauschii - Xinpeng Zhao; Linlin Lv; Jiahui Li; Feifei Ma; Shenglong Bai; Yun Zhou; Dale Zhang; Suoping Li; Chun-peng Song (Euphytica, 2021)

Effects of sodium arsenite and dimethyl arsenic acid on Liaoning cashmere goat skin fibroblasts - Fengqin Zhao; Chuang Wang; Dongyu Sun; Linlin Zhang; Zhiyue Wang; Jun Piao; Jingai Piao; Mei Jin (Environmental Science and Pollution Research, 2021)

Biochar Derived from Treated Lotus Stem and Adsorption of Phthalic Acid Esters - Ruiling Zhang; Linlin Chen; Binbin Qiu; Xiaojing Sun; Songyan Qin; Bo Wang; Feiyue Li; Lixin Zhao; Zhe Zhu (Water, Air, & Soil Pollution, 2021)

Long non-coding RNA HCG18 promotes M1 macrophage polarization through regulating the miR-146a/TRAF6 axis, facilitating the progression of diabetic peripheral neuropathy - Wei Ren; Guangxia Xi; Xing Li; Lingxia Zhao; Kun Yang; Xuemei Fan; Linlin Gao; Hongmei Xu; Jianjin Guo (Molecular and Cellular Biochemistry, 2021)

Evaluation and spatiotemporal characteristics of glacier service value in the Qilian Mountains - Meiping Sun; Weiqian Ma; Xiaojun Yao; Linlin Zhao; Zhongqin Li; Dahe Qin (Journal of Geographical Sciences, 2020)

Controlled synchronization of prolactin/STAT5 and AKT1/mTOR in bovine mammary epithelial cells - Baosheng Wang; Linlin Shi; Jingjing Men; Qingzhang Li; Xiaoming Hou; Chunmei Wang; Feng Zhao (In Vitro Cellular & Developmental Biology - Animal, 2020)

Cutibacterium acnes Type II strains are associated with acne in Chinese patients - Shuyang Zhao; Jiayu Ci; Jinhui Xue; Yaofeng Wang; Xuelong Li; Linlin Hao; Liu Tian; Haiyan Guo; Chengqi Xin; Yujie Zhao (Antonie van Leeuwenhoek, 2020)

Four superoxide dismutases of Bacillus cereus 0–9 are non-redundant and perform different functions in diverse living conditions - Juanmei Zhang; Haodong Wang; Qiubin Huang; Ying Zhang; Linlin Zhao; Fengying Liu; Gang Wang (World Journal of Microbiology and Biotechnology, 2020)

Gelatin Methacrylate (GelMA)-Based Hydrogels for Cell Transplantation: an Effective Strategy for Tissue Engineering - Shining Xiao; Tengfei Zhao; Jingkai Wang; Chenggui Wang; Jiangnan Du; Liwei Ying; Jiangtao Lin; Caihua Zhang; Wanglu Hu; Linlin Wang; Kan Xu (Stem Cell Reviews and Reports, 2019)

Effects of drought–re-watering–drought on the photosynthesis physiology and secondary metabolite production of Bupleurum chinense DC. - Linlin Yang; Yu Zhao; Qi Zhang; Lin Cheng; Mei Han; Yueying Ren; Limin Yang (Plant Cell Reports, 2019)

Electrosorptive removal of salt ions from water by membrane capacitive deionization (MCDI): characterization, adsorption equilibrium, and kinetics - Guiju Li; Wenbo Cai; Ruihua Zhao; Linlin Hao (Environmental Science and Pollution Research, 2019)

Sodium Fluoride (NaF) Induces Inflammatory Responses Via Activating MAPKs/NF-κB Signaling Pathway and Reducing Anti-inflammatory Cytokine Expression in the Mouse Liver - Linlin Chen; Ping Kuang; Huan Liu; Qin Wei; Hengmin Cui; Jing Fang; Zhicai Zuo; Junliang Deng; Yinglun Li; Xun Wang; Ling Zhao (Biological Trace Element Research, 2019)

Heat Transfer in Sandstones at Low Temperature - Zhiqiang Liu; Linlin Wang; Bo Zhao; Jingyi Leng; Guangqing Zhang; Diansen Yang (Rock Mechanics and Rock Engineering, 2019)

Development of genome-wide SNPs for population genetics of Collichthys lucidus - Linlin Zhao; Meijie Jiang; Fangyuan Qu; Dan Yi; Shouqiang Wang; Zhaohui Zhang (Conservation Genetics Resources, 2018)

Spirillospora tritici sp. nov., a Novel Actinomycete Isolated from Rhizosphere Soil of Triticum aestivum L. - Jing Song; Jiabin Wang; Tianyu Sun; Chuang Li; Hairong He; Linlin Shi; Xiaowei Guo; Junwei Zhao; Wensheng Xiang (Current Microbiology, 2018)

Adsorptive removal of organics from aqueous phase by acid-activated coal fly ash: preparation, adsorption, and Fenton regenerative valorization of “spent” adsorbent - Nannan Wang; Linlin Hao; Jiaqing Chen; Qiang Zhao; Han Xu (Environmental Science and Pollution Research, 2018)

5-Azacytidine treatment and TaPBF-D over-expression increases glutenin accumulation within the wheat grain by hypomethylating the Glu-1 promoters - Jiantang Zhu; Linlin Fang; Jiaqi Yu; Ying Zhao; Fanguo Chen; Guangmin Xia (Theoretical and Applied Genetics, 2018)

Time-Dependent Lactate Production and Amino Acid Utilization in Cultured Astrocytes Under High Glucose Exposure - Dan Wang; Liangcai Zhao; Hong Zheng; Minjian Dong; Linlin Pan; Xi Zhang; Huajie Zhang; Hongchang Gao (Molecular Neurobiology, 2018)

Definition and classification system of glacial lake for inventory and hazards study - Xiaojun Yao; Shiyin Liu; Lei Han; Meiping Sun; Linlin Zhao (Journal of Geographical Sciences, 2018)

Plantactinospora solaniradicis sp. nov., a novel actinomycete isolated from the root of a tomato plant (Solanum lycopersicum L.) - Wenchao Li; Xiaowei Guo; Linlin Shi; Junwei Zhao; Liangliang Yan; Xiaotong Zhong; Chen Zhang; Yufei Chen; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

Identification and Functional Analysis of Two Cotton Orthologs of MAX2 Which Control Shoot Lateral Branching - Linlin Zhao; Jingjing Fang; Jin Xing; Weina Liu; Peng Peng; Haixin Long; Jinfeng Zhao; Wenhui Zhang; Xueyong Li (Plant Molecular Biology Reporter, 2017)

miR-155 promotes cutaneous wound healing through enhanced keratinocytes migration by MMP-2 - Longlong Yang; Zhao Zheng; Qin Zhou; Xiaozhi Bai; Lei Fan; Chen Yang; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

Exosomes derived from human amniotic epithelial cells accelerate wound healing and inhibit scar formation - Bin Zhao; Yijie Zhang; Shichao Han; Wei Zhang; Qin Zhou; Hao Guan; Jiaqi Liu; Jihong Shi; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

Gelatin microspheres containing calcitonin gene-related peptide or substance P repair bone defects in osteoporotic rabbits - Jianghao Chen; Wei Liu; Jinxiu Zhao; Cong Sun; Jie Chen; Kaijin Hu; Linlin Zhang; Yuxiang Ding (Biotechnology Letters, 2017)

In Vivo Exposure of Kaempferol Is Driven by Phase II Metabolic Enzymes and Efflux Transporters - Liang Zheng; Lijun Zhu; Min Zhao; Jian Shi; Yuhuan Li; Jia Yu; Huangyu Jiang; Jinjun Wu; Yunli Tong; Yuting Liu; Ming Hu; Linlin Lu; et al. (The AAPS Journal, 2016)

Characterization of chromophoric dissolved organic matter and relationships among PARAFAC components and water quality parameters in Heilongjiang, China - Hongyang Cui; Jianhong Shi; Linlin Qiu; Yue Zhao; Zimin Wei; Xinglei Wang; Liming Jia; Jiming Li (Environmental Science and Pollution Research, 2016)

Allogeneic adipose-derived stem cells promote survival of fat grafts in immunocompetent diabetic rats - Jun Zhang; Xiaozhi Bai; Bin Zhao; Yunchuan Wang; Linlin Su; Peng Chang; Xujie Wang; Shichao Han; Jianxin Gao; Xiaolong Hu; Dahai Hu; Xiaoyan Liu (Cell and Tissue Research, 2016)

Bioavailability of riverine dissolved organic carbon and nitrogen in the Heilongjiang watershed of northeastern China - Jianhong Shi; Hongyang Cui; Liming Jia; Linlin Qiu; Yue Zhao; Zimin Wei; Junqiu Wu; Xin Wen (Environmental Monitoring and Assessment, 2016)

MRP1 knockdown down-regulates the deposition of collagen and leads to a reduced hypertrophic scar fibrosis - Yan Li; Longlong Yang; Zhao Zheng; Jihong Shi; Xue Wu; Hao Guan; Yanhui Jia; Ke Tao; Hongtao Wang; Shichao Han; Jianxin Gao; Bin Zhao; et al. (Journal of Molecular Histology, 2015)

Association of interleukin-6 gene polymorphism with coronary artery disease: an updated systematic review and cumulative meta-analysis - Haifeng Hou; Chenglin Wang; Fengjing Sun; Linlin Zhao; Aishe Dun; Zheng Sun (Inflammation Research, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

Selenium Deficiency Influences the Gene Expressions of Heat Shock Proteins and Nitric Oxide Levels in Neutrophils of Broilers - Xi Chen; Haidong Yao; Linlin Yao; Jinxin Zhao; Yilin Luan; Ziwei Zhang; Shiwen Xu (Biological Trace Element Research, 2014)

Cloning and functional analysis of two flavanone-3-hydroxylase genes from Reaumuria trigyna - Huirong Zhang; Lixia Zhao; Jia Wang; Linlin Zheng; Zhenhua Dang; Yingchun Wang (Acta Physiologiae Plantarum, 2014)

Potential short-term effects of yak and Tibetan sheep dung on greenhouse gas emissions in two alpine grassland soils under laboratory conditions - Yanjiang Cai; Xiaodan Wang; Weixin Ding; Linlin Tian; Hui Zhao; Xuyang Lu (Biology and Fertility of Soils, 2013)

Climate–growth analysis of Qilian juniper across an altitudinal gradient in the central Qilian Mountains, northwest China - Linlin Gao; Xiaohua Gou; Yang Deng; Wenhuo Liu; Meixue Yang; Zhiqian Zhao (Trees, 2013)

Influence of algal bloom degradation on nutrient release at the sediment–water interface in Lake Taihu, China - Mengyuan Zhu; Guangwei Zhu; Linlin Zhao; Xin Yao; Yunlin Zhang; Guang Gao; Boqiang Qin (Environmental Science and Pollution Research, 2013)

Effect of mechanical stretch on the expressions of elastin, LOX and Fibulin-5 in rat BMSCs with ligament fibroblasts co-culture - Zhao Bing; Liang Linlin; Yan Jianguo; Ren Shenshen; Ren Ruifang; Zhang Xi (Molecular Biology Reports, 2012)

Effects of Aluminum Exposure on Serum Sex Hormones and Androgen Receptor Expression in Male Rats - Hao Sun; Chongwei Hu; Linlin Jia; Yanzhu Zhu; Hansong Zhao; Bing Shao; Nan Wang; Zhigang Zhang; Yanfei Li (Biological Trace Element Research, 2011)

FaRE1: a transcriptionally active Ty1-copia retrotransposon in strawberry - Ping He; Yue Ma; Guiling Zhao; Hongyan Dai; He Li; Linlin Chang; Zhihong Zhang (Journal of Plant Research, 2010)

Determination of Phthalate Esters in Soil Samples by Microwave Assisted Extraction and High Performance Liquid Chromatography - Pei Liang; Linlin Zhang; Lili Peng; Qian Li; Ehong Zhao (Bulletin of Environmental Contamination and Toxicology, 2010)

Isolation of two novel complete Ty1-copia retrotransposons from apple and demonstration of use of derived S-SAP markers for distinguishing bud sports of Malus domestica cv. Fuji - Guiling Zhao; Hongyan Dai; Linlin Chang; Yue Ma; Haiyue Sun; Ping He; Zhihong Zhang (Tree Genetics & Genomes, 2010)

Increased expression of CDK11p58 and cyclin D3 following spinal cord injury in rats - Yuhong Ji; Feng Xiao; Linlin Sun; Jing Qin; Shuxian Shi; Junling Yang; Yonghua Liu; Dan Zhou; Jian Zhao; Aiguo Shen (Molecular and Cellular Biochemistry, 2008)

Lipopolysaccharide-Induced Upregulation of Tumor Necrosis Factor-α (TNF-α) and TNF Receptors in Rat Sciatic Nerve - Youhua Wang; Dan Zhou; Qin Shen; Chun Cheng; Hai-ou Liu; Yongwei Qin; Linlin Sun; Feng Xiao; Jian Zhao; Aiguo Shen (Journal of Molecular Neuroscience, 2007)

A diagnostic study of heavy rainfall in karachi due to merging of a mesoscale low and a diffused tropical depression during South Asian summer monsoon - Ghulam Rasul; Qamar-uz-Zaman Chaudhry; Zhao Sixiong; Zeng Qingcun; Qi Linlin; Zhang Gaoying (Advances in Atmospheric Sciences, 2005)

An analysis of a meso-β system in a mei-yu front using the intensive observation data during CHeRES 2002 - Sun Jianhua; Zhang Xiaoling; Qi Linlin; Zhao Sixiong (Advances in Atmospheric Sciences, 2005)